Flexographic printing original plate and method for producing flexographic printing plate

By introducing an intermediate layer of hydrophilic resin and inorganic layered compounds into the flexible printing original, combined with laser ablation and embossing exposure technology, the problem of difficult to take into account the size and depth of printing points in the prior art is solved, and high-fine printing is achieved , and improves the quality and production efficiency of the printed materials by optimizing the washing process.

CN113168090BActive Publication Date: 2024-12-27ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980077756.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-10
Filing Date
2019-12-09
Publication Date
2024-12-27
Estimated Expiration
2039-12-09

AI Technical Summary

Technical Problem

The existing flexible printing originals are difficult to achieve deep relief images when forming small-sized printing points, and the infrared ablation layer is prone to pinholes, affecting the quality of the printed materials.

Method used

An intermediate layer containing a hydrophilic resin and an inorganic layered compound is arranged between the photosensitive resin composition layer and the infrared ablation layer, and a high-fine printing point is formed by laser ablation and embossing exposure technology, and developed by water system. The liquid is optimized for washing to remove unexposed parts.

Benefits of technology

It realizes a flexible printing original with excellent pinhole resistance and high washing ability and a flexible printing plate with excellent printing characteristics, which can form high-fine and bright areas of printing, and improves the quality and production efficiency of the printed materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003084459160000511
    Figure BDA0003084459160000511
  • Figure BDA0003084459160000521
    Figure BDA0003084459160000521
Patent Text Reader

Abstract

A flexographic printing plate, which is a flexographic printing plate formed by laminating at least a support, a photosensitive resin composition layer, an intermediate layer and an infrared ablation layer in sequence, wherein the intermediate layer contains a hydrophilic resin (A) and an inorganic layered compound (B), and the film thickness of the intermediate layer is greater than 2 μm and less than 30 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a flexographic printing original plate and a flexographic printing plate. Background Art

[0002] Flexographic printing is a type of relief printing. Since the flexographic printing plate uses soft materials such as rubber and synthetic resin, it has the advantage of being applicable to a variety of printed materials.

[0003] Conventionally, there are two methods for producing flexographic printing plates used in flexographic printing: a method using negative platemaking; and a method using computer platemaking technology (hereinafter referred to as CTP technology) in which information processed on a computer is directly drawn on a printing plate to produce a relief.

[0004] In the method using the aforementioned CTP technology, there is no need for a negative film manufacturing process, which can reduce the cost and time required for negative film manufacturing. Therefore, the method using the CTP technology has become increasingly mainstream in recent years.

[0005] When using CTP technology, a flexographic printing plate original (hereinafter sometimes referred to as a flexographic printing original) is generally a plate obtained by laminating a photosensitive resin composition layer, a protective layer (barrier layer), and an infrared ablative layer in this order on a substrate of PET resin or the like.

[0006] The flexographic printing plate is produced, for example, as follows.

[0007] First, ultraviolet rays are irradiated onto the entire surface of the photosensitive resin composition layer through a substrate formed of a film such as a PET resin to perform back exposure, thereby providing a uniform cured layer.

[0008] Next, the infrared ablation layer on the photosensitive resin composition layer is irradiated with laser light for drawing, thereby removing part of the infrared ablation layer to prepare an image mask.

[0009] Furthermore, relief exposure is performed by irradiating the photosensitive resin composition layer with ultraviolet rays through the above-mentioned pattern mask, thereby photocuring the portion where the infrared ablation layer has been removed.

[0010] Then, the unexposed portion (ie, the portion not photocured) of the photosensitive resin composition layer is removed to form a relief image as a desired image, thereby obtaining a flexographic printing plate.

[0011] A relief image contains a plurality of printing dots. The shape of the printing dots and the depth of the relief affect the image quality of the printed matter. In recent years, there is a high demand for high-definition printed matter. In addition, printed matter with bright areas of the image (commonly called highlights) is sought. In order to appropriately express the highlight area, it is necessary to print very small-sized printing dots.

[0012] Under the above background, there is a demand for a flexographic printing plate that can realize a relief image with a deep relief depth while forming dots of a microscopic size.

[0013] However, when a flexographic printing plate is irradiated with ultraviolet rays for relief exposure, if oxygen is present, oxygen radicals generated from the oxygen inhibit the photocuring reaction of the photosensitive resin composition, and the photocuring of the photosensitive resin composition layer is insufficient.

[0014] Therefore, the following technologies have been disclosed in the past: a technology for adjusting the shape of printed dots; and a technology for laminating a laser-ablated mask layer on a photosensitive resin composition layer to provide a printed dot structure having a flat top and a steep shoulder (see, for example, Patent Documents 1 and 2).

[0015] There is also disclosed a technique of providing one or more barrier layers on a flexographic printing plate in order to cover the surface of a photosensitive resin composition layer having adhesiveness and to block oxygen in the atmosphere (see, for example, Patent Document 3).

[0016] Furthermore, in order to realize a relief image having a deep relief depth while forming dots of a microscopic size, it is important that the infrared ablation layer has no defects (pinholes).

[0017] When pinholes exist in the infrared ablation layer, the photosensitive resin composition layer in contact with the pinholes is exposed during relief exposure, thereby causing unintended image formation, resulting in the following problems: micro dots cannot be formed, or unintended shallow relief is formed.

[0018] As a method for forming the infrared ablation layer, in addition to a method of directly applying the infrared ablation layer to the photosensitive resin composition layer, there is also a method of applying the infrared ablation layer on a cover sheet, laminating the infrared ablation layer side to the photosensitive resin composition layer, and performing transfer and lamination.

[0019] In the case of forming an infrared ablation layer by laminating an infrared ablation layer coated on a cover sheet with a photosensitive resin composition layer, pinholes may be generated not only due to uneven coating and pitting when the infrared ablation layer is coated on the cover sheet, but also due to impact during storage and transportation of the cover sheet coated with the infrared ablation layer, or due to the lamination temperature, pressure, or photosensitive resin composition being kneaded and extruded when laminating with the photosensitive resin composition layer.

[0020] In view of the above, a technique has been proposed to provide a protective layer (barrier layer) having oxygen barrier properties and a function of protecting an infrared ablation layer.

[0021] As a barrier layer having oxygen barrier properties, a polyvinyl alcohol resin layer is generally known.

[0022] However, films formed of polyvinyl alcohol resins have problems such as poor bending resistance and easy formation of cracks and wrinkles. Flexographic printing plates are required to be flexible in nature, and there are problems when using polyvinyl alcohol resins such as the above.

[0023] In response to this, a technique for adjusting the film thickness and Young's modulus of the resin of the barrier layer has been proposed (see, for example, Patent Documents 4 and 5).

[0024] Prior art literature

[0025] Patent Literature

[0026] Patent Document 1: Japanese Patent Application No. 2014-512576

[0027] Patent Document 2: Japanese Patent Application No. 2014-507677

[0028] Patent Document 3: Japanese Patent Publication No. 7-506201

[0029] Patent Document 4: Japanese Patent No. 4332865

[0030] Patent Document 5: Japanese Patent No. 5573675 Summary of the invention

[0031] Problem that the invention aims to solve

[0032] However, although the polyvinyl alcohol resin proposed in Patent Documents 4 and 5 can form a protective layer with excellent oxygen barrier properties, it is inherently prone to cracking and wrinkling. In particular, when the infrared ablation layer is formed by laminating the infrared ablation layer coated on the cover sheet together with the protective layer and the photosensitive resin composition layer, the protective layer is easily destroyed, pinholes are generated in the infrared ablation layer, and the intended oxygen barrier properties cannot be exhibited. There is a problem that a flexible printing plate sufficient for realizing a relief image with a deep relief depth while forming micro-sized dots cannot be obtained.

[0033] Therefore, in view of the above-mentioned problems of the prior art, an object of the present invention is to provide a flexographic printing plate having excellent pinhole resistance and high washability, and a method for producing a flexographic printing plate having excellent printing properties using the flexographic printing plate.

[0034] Solutions for solving problems

[0035] The present inventors conducted intensive research to solve the above-mentioned problems and found that by setting an intermediate layer containing a hydrophilic resin and an inorganic layered compound between a photosensitive resin composition layer and an infrared ablation layer in a flexible printing original plate, it is possible to form a relief image with a deep relief depth while forming tiny-sized dots, and to obtain a flexible printing plate with high precision and capable of printing high-brightness areas, thereby completing the present invention.

[0036] That is, the present invention is as follows.

[0037] [1] A flexographic printing plate, wherein at least a support, a photosensitive resin composition layer, an intermediate layer, and an infrared ablative layer are laminated in this order,

[0038] The intermediate layer contains a hydrophilic resin (A) and an inorganic layered compound (B).

[0039] The intermediate layer has a thickness of 2 μm or more and 30 μm or less.

[0040] [2] The flexographic printing plate according to [1] above, wherein the intermediate layer contains 0.1 to 20 parts by mass of the inorganic stratiform compound (B) based on 100 parts by mass of the hydrophilic resin (A).

[0041] [3] The flexographic printing plate according to [1] or [2], wherein the inorganic layered compound (B) is water-swellable synthetic mica.

[0042] [4] The flexographic printing original plate according to any one of [1] to [3] above, wherein the intermediate layer further contains a water-dispersible latex (C).

[0043] [5] The flexographic printing plate according to [4], wherein the intermediate layer contains 5 to 45 parts by mass of the water-dispersible latex (C) based on 100 parts by mass of the hydrophilic resin (A).

[0044] [6] The flexographic printing plate according to any one of [1] to [5], wherein the gel fraction of the intermediate layer calculated by the following formula is 10 to 90% or less,

[0045] Gel fraction (%)=(mass of the intermediate layer immersed in pure water at room temperature for 72 hours and then dried at 50°C for 3 hours / mass of the intermediate layer before immersion in pure water)×100.

[0046] [7] A method for manufacturing a flexographic printing plate, comprising the following steps:

[0047] A step of laser ablating the infrared ablation layer of the flexographic printing plate according to any one of [1] to [6] to form a negative pattern;

[0048] A step of selectively exposing the photosensitive resin composition layer through the negative pattern; and

[0049] A step of removing the unexposed portion of the photosensitive resin composition layer.

[0050] Effects of the Invention

[0051] According to the present invention, there can be provided a flexographic printing original plate having excellent pinhole resistance and high washability, and a method for producing a flexographic printing plate having excellent printing characteristics using the flexographic printing original plate. DETAILED DESCRIPTION

[0052] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as “this embodiment”) will be described in detail, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the invention.

[0053] [Flexographic printing plate]

[0054] The flexographic printing plate of the present embodiment is a flexographic printing plate in which at least a support, a photosensitive resin composition layer, an intermediate layer, and an infrared ablation layer are sequentially stacked.

[0055] The intermediate layer contains a hydrophilic resin (A) and an inorganic layered compound (B).

[0056] The intermediate layer has a thickness of 2 μm or more and 30 μm or less.

[0057] The flexographic printing plate of this embodiment only needs to have a support, a photosensitive resin composition layer, an intermediate layer, and an infrared ablation layer as essential structures, and at least these layers are stacked in the above order. Functional layers such as adhesive layers can also be appropriately provided between these layers.

[0058] (Supporting body)

[0059] The support used in the flexographic printing plate of the present embodiment is not particularly limited, and examples thereof include polypropylene films, polyethylene films, polyester films such as polyethylene terephthalate and polyethylene naphthalate, and polyamide films.

[0060] As the support, a dimensionally stable polyester film having a thickness of 75 μm to 300 μm is preferred.

[0061] In addition, it is preferable to have an adhesive layer on the support.

[0062] Examples of the material of the adhesive layer include a composition having a binder polymer such as polyurethane, polyamide, or thermoplastic elastomer, and an adhesive active ingredient such as an isocyanate compound or an ethylenically unsaturated compound.

[0063] Furthermore, various auxiliary additive components such as a plasticizer, a thermal polymerization inhibitor, an ultraviolet absorber, an antihalation agent, a light stabilizer, a photopolymerization initiator, a photopolymerizable monomer, a dye, etc. may be added to the adhesive layer.

[0064] Furthermore, in order to obtain a higher adhesive force, it is more preferable to provide at least one primer layer between the adhesive layer and the polyester film as a support.

[0065] (Photosensitive resin composition layer)

[0066] Preferred examples of materials constituting the photosensitive resin composition layer of the flexographic printing plate of the present embodiment include photosensitive resin compositions containing (a) a thermoplastic elastomer, (b) a hydrophilic copolymer, (c) a photopolymerizable monomer, and (d) a photopolymerization initiator.

[0067] As the compounds (a) to (d) above, for example, compounds described in “Japanese Patent Application Laid-Open No. 2018-120131” can be used.

[0068] <(a) Thermoplastic elastomer>

[0069] The (a) thermoplastic elastomer is preferably a thermoplastic elastomer containing at least one polymer segment mainly composed of a conjugated diene and at least one polymer segment mainly composed of a vinyl aromatic hydrocarbon.

[0070] The term "mainly" used throughout this specification means 60% by mass or more in the polymer segment.

[0071] In the polymer segment mainly composed of a conjugated diene, the conjugated diene preferably accounts for 80% by mass or more, more preferably 90% by mass or more, of the polymer segment.

[0072] The conjugated diene is not limited to the following, and examples thereof include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, and chloroprene monomers, and 1,3-butadiene is particularly preferred from the viewpoint of wear resistance. These monomers may be used alone or in combination of two or more.

[0073] The vinyl content in the total amount of conjugated dienes in the polymer segment mainly composed of conjugated dienes, such as 1,2-butadiene and 3,4-isoprene, is not particularly limited. From the viewpoint of printing plate formability, the vinyl content is preferably 5 mol% to 50 mol%, more preferably 8 mol% to 50 mol%, and further preferably 10 mol% to 40 mol%.

[0074] The number average molecular weight of the polymer segment mainly composed of a conjugated diene is preferably 20,000 to 250,000, more preferably 30,000 to 200,000, and even more preferably 40,000 to 150,000, from the viewpoint of printing durability.

[0075] The polymer segment with conjugated diene as the main body may contain alkylene units. There is no particular limitation on the method for introducing the alkylene units, and examples thereof include a method of polymerizing monoolefins such as ethylene and butene as the raw material monomer of the polymer segment with conjugated diene as the main body; a method of hydrogenating the conjugated diene polymer segment, etc. In particular, from the viewpoint of ease of acquisition, a method of hydrogenating the polymer segment with conjugated diene as the main body is preferred.

[0076] The content of the alkylene unit in the polymer segment mainly composed of a conjugated diene is preferably 5 mol% or more from the viewpoint of solvent resistance, and is preferably 50 mol% or less from the viewpoint of ensuring the transparency of the resin composition. It is more preferably in the range of 10 mol% to 35 mol%, and further preferably in the range of 10 mol% to 25 mol%.

[0077] The aforementioned alkylene unit is preferably contained in a polymer segment with butadiene as the main body. In addition, it is more preferred that the polymer segment with butadiene as the main body is partially hydrogenated to contain all 1,4-butadiene units, 1,2-butadiene (vinyl) units and butylene (alkylene) units. In addition, it is further preferred that the polymer segment with butadiene as the main body contains at least 1,4-butadiene units in the range of 25 mol% to 70 mol%, 1,2-butadiene (vinyl) units in the range of 0 mol% to 50 mol%, and butylene units in the range of 10 mol% to 50 mol%.

[0078] It should be noted that the content and ratio of conjugated diene, vinyl content of conjugated diene and vinyl aromatic hydrocarbon can be measured using a nuclear magnetic resonance device ( 1 H-NMR) determination.

[0079] Examples of the vinyl aromatic hydrocarbon include monomers such as styrene, tert-butylstyrene, divinylbenzene, 1,1-diphenylstyrene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, vinylpyridine, p-methylstyrene, tert-butylstyrene, α-methylstyrene, and 1,1-diphenylethylene. In particular, styrene is preferred from the viewpoint of being able to smoothly mold a flexographic printing plate at a relatively low temperature (hereinafter referred to as high moldability). These monomers may be used alone or in combination of two or more.

[0080] The number average molecular weight of the polymer segment mainly composed of vinyl aromatic hydrocarbons is preferably 100,000 or less from the viewpoint of preventing the printing plate from exhibiting orientation, and is preferably 3,000 or more from the viewpoint of defect resistance during plate making and printing. The number average molecular weight of the polymer segment mainly composed of vinyl aromatic hydrocarbons is more preferably in the range of 5,000 to 80,000, and further preferably in the range of 5,000 to 60,000.

[0081] The content of the vinyl aromatic hydrocarbon in the block copolymer is preferably 25% by mass or less from the viewpoint of high moldability of the photosensitive resin composition, high resistance to defect of the convex portion of the printing plate, and high hardness of the printing plate when the ink component is attached. On the other hand, from the viewpoint of improving the cold flow resistance of the flexographic printing original plate, it is preferably 13% by mass or more. It is more preferably in the range of 15% to 24% by mass, and further preferably in the range of 16% to 23% by mass.

[0082] The content of the thermoplastic elastomer (a) in the photosensitive resin composition layer is preferably 15% to 90% by mass when the total amount of the photosensitive resin composition is 100% by mass from the viewpoint of printing durability during printing. The content of the thermoplastic elastomer (a) is more preferably 15% to 80% by mass, and further preferably 20% to 75% by mass.

[0083] <(b) Hydrophilic copolymer>

[0084] (b) Hydrophilic copolymer refers to polymer particles formed by internal crosslinking of units derived from hydrophilic unsaturated monomers. Examples of such polymer particles include polymer particles obtained by emulsion polymerization using hydrophilic unsaturated monomers and other monomers copolymerizable therewith as needed, dispersing the polymer particles as a dispersoid in water to obtain a water-dispersible latex, and removing water from the water-dispersible latex. The units derived from the hydrophilic unsaturated monomers may account for, for example, 0.1 to 20% by mass, 0.5 to 15% by mass, or 1 to 10% by mass in the total monomers.

[0085] As the hydrophilic unsaturated monomer, a monomer containing at least one hydrophilic group and an unsaturated double bond is preferred. Examples of the hydrophilic unsaturated monomer include monomers containing unsaturated double bonds such as carboxylic acid groups, sulfonic acid groups, phosphoric acid groups, and their salts, and acid anhydride groups; monomers containing hydroxyl groups and unsaturated double bonds; monomers containing acrylamide and unsaturated double bonds; surfactants (monomers) containing reactive unsaturated double bonds; and the like. These hydrophilic unsaturated monomers may be used alone or in combination of two or more.

[0086] Examples of the water-dispersible latex include water-dispersible latex polymers such as acrylonitrile-butadiene copolymer latex, polychloroprene latex, polyisoprene latex, polyurethane latex, (meth)acrylate-butadiene latex, vinylpyridine polymer latex, butyl polymer latex, polysulfide rubber polymer latex, and acrylate polymer latex.

[0087] In addition, it is preferred that these water-dispersible latexes are copolymerized with one or more unsaturated monomers having an acidic functional group, such as (meth)acrylates, carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, vinyl benzoic acid, and cinnamic acid, monobasic acids such as sulfonic acids such as styrene sulfonic acid; dibasic acids such as itaconic acid, fumaric acid, maleic acid, citraconic acid, and muconic acid; and water-dispersible latex polymers.

[0088] It should be noted that the water-dispersible latex may contain other polymer particles as dispersoids in addition to the polymer particles obtained by emulsion polymerization using hydrophilic unsaturated monomers and other monomers copolymerizable therewith as required. Such other polymer particles include particles of polybutadiene, natural rubber, and styrene-butadiene copolymers.

[0089] Among these water-dispersible latexes, water-dispersible latexes containing a butadiene skeleton or an isoprene skeleton in the molecular chain of the polymer are preferred from the viewpoint of printing resistance. For example, polybutadiene latex, styrene-butadiene copolymer latex, acrylonitrile-butadiene copolymer latex, and water-dispersible latexes obtained by copolymerizing these water-dispersible latexes with (meth)acrylate, acrylic acid, methacrylic acid, itaconic acid, etc. are preferred. As the water-dispersible latex, a water-dispersible latex of a copolymer obtained by copolymerizing a styrene-butadiene copolymer with one or more unsaturated monomers containing an acidic functional group, such as (meth)acrylate, acrylic acid, methacrylic acid, itaconic acid, etc. is more preferred.

[0090] The amount of the unsaturated monomer containing an acidic functional group is preferably 1 to 30% by weight of the total amount of the unsaturated monomers used in the synthesis of the hydrophilic copolymer (b). When the amount is 1% by weight or more, there is a tendency for water-based development to become easier, and when it is 30% by weight or less, an increase in the amount of moisture absorption of the photosensitive resin composition and an increase in the amount of swelling of the ink can be prevented, and deterioration in the processability of the photosensitive resin composition during mixing can be prevented.

[0091] Unsaturated monomers other than unsaturated monomers containing acidic functional groups that can be used in the synthesis of the (b) hydrophilic copolymer are not limited to the following, and examples thereof include conjugated dienes, aromatic vinyl compounds, (meth)acrylates, vinyl monocarboxylic acid alkyl ester monomers having a hydroxyl group, unsaturated dibasic acid alkyl esters, maleic anhydride, vinyl cyanide compounds, (meth)acrylamide and its derivatives, vinyl esters, vinyl ethers, vinyl halides, basic monomers having an amino group, vinyl pyridine, olefins, silicon-containing α,β-ethylenically unsaturated monomers, and allyl compounds.

[0092] Examples of the conjugated diene include, but are not limited to, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-butadiene, 1,3-pentadiene, chloroprene, 2-chloro-1,3-butadiene, and cyclopentadiene.

[0093] Examples of the aromatic vinyl compound include, but are not limited to, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, vinyltoluene, vinylxylene, bromostyrene, vinylbenzyl chloride, p-tert-butylstyrene, chlorostyrene, alkylstyrene, divinylbenzene, trivinylbenzene, and the like.

[0094] Examples of the (meth)acrylate include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, and Benzyl acrylate, 2-ethyl-hexyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxycyclohexyl (meth)acrylate, glycidyl (meth)acrylate, ethylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate , diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, allyl (meth)acrylate, bis(4-acryloxypolyethoxyphenyl)propane, methoxypolyethylene glycol (meth)acrylate, β-(meth)acryloxyethyl hydrogenated phthalate, β-(meth)acryl Oxyethyl hydrogenated succinate, 3-chloro-2-hydroxypropyl (meth)acrylate, stearyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-1,3-di(meth)acryloyloxypropane, 2,2-bis[4-((meth)acryloyloxyethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloyloxy-diethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloyloxy-polyethoxy)phenyl]propane, isobornyl (meth)acrylate, and the like.

[0095] Examples of the vinyl monocarboxylic acid alkyl ester monomer having a hydroxyl group include, but are not limited to, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 1-hydroxypropyl acrylate, 1-hydroxypropyl methacrylate, and hydroxycyclohexyl (meth)acrylate.

[0096] Examples of the unsaturated dibasic acid alkyl ester include, but are not limited to, crotonic acid alkyl ester, itaconic acid alkyl ester, fumaric acid alkyl ester, and maleic acid alkyl ester.

[0097] Examples of the vinyl cyanide compound include, but are not limited to, acrylonitrile, methacrylonitrile, and the like.

[0098] Examples of (meth)acrylamide and derivatives thereof include, but are not limited to, (meth)acrylamide, N-methylol (meth)acrylamide, and N-alkoxy (meth)acrylamide.

[0099] Examples of the vinyl esters include, but are not limited to, vinyl acetate, vinyl butyrate, vinyl stearate, vinyl laurate, vinyl myristate, vinyl propionate, and vinyl versatate.

[0100] Examples of the vinyl ethers include, but are not limited to, methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, pentyl vinyl ether, and hexyl vinyl ether.

[0101] Examples of the vinyl halides include, but are not limited to, vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, and vinylidene fluoride.

[0102] Examples of the basic monomer having an amino group include, but are not limited to, aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.

[0103] Examples of the olefin include, but are not limited to, ethylene and the like.

[0104] Examples of the silicon-containing α,β-ethylenically unsaturated monomer include, but are not limited to, vinyltrichlorosilane and vinyltriethoxysilane.

[0105] Examples of the allyl compound include, but are not limited to, allyl esters and diallyl phthalate.

[0106] In addition, a monomer having three or more double bonds such as triallyl isocyanurate may also be used.

[0107] These monomers may be used alone or in combination of two or more. The mass ratio of the acidic functional group-containing unsaturated monomer to other monomers (acidic functional group-containing unsaturated monomer / other monomers) is preferably 5 / 95 to 95 / 5, more preferably 50 / 50 to 90 / 10.

[0108] By setting the ratio to 5 / 95 to 95 / 5, the rubber elasticity of the photosensitive resin composition can be made practically favorable.

[0109] The (b) hydrophilic copolymer is preferably a polymer synthesized by emulsion polymerization. In this case, the emulsifier (surfactant) used in the polymerization is preferably a reactive emulsifier.

[0110] As the reactive emulsifier, it is preferred that the reactive emulsifier has a free radical polymerizable double bond, a hydrophilic functional group and a hydrophobic group in the molecular structure and has emulsification, dispersing and wetting functions like a common emulsifier. In addition, when the (b) hydrophilic copolymer is subjected to emulsion polymerization, it is preferred to use the following emulsifier (surfactant): the emulsifier can synthesize a polymer with an average particle size of 5 to 500 nm when 0.1 mass part or more of the reactive emulsifier is used relative to 100 mass parts of the unsaturated monomer containing an acidic functional group and other monomers other than the reactive emulsifier.

[0111] Examples of the radical polymerizable double bond structure in the molecular structure of the reactive emulsifier include a vinyl group, an acryloyl group, and a methacryloyl group.

[0112] Examples of the hydrophilic functional group in the molecular structure of the reactive emulsifier include anionic groups such as sulfate, nitric acid, phosphoric acid, boric acid, and carboxyl groups; cationic groups such as amino groups; polyoxyalkylene chain structures such as polyoxyethylene, polyoxymethylene, and polyoxypropylene groups; or hydroxyl groups.

[0113] Examples of the hydrophobic group in the molecular structure of the reactive emulsifier include an alkyl group and a phenyl group.

[0114] Reactive emulsifiers include anionic emulsifiers, nonionic emulsifiers, cationic emulsifiers, amphoteric emulsifiers, etc., depending on the type of hydrophilic functional group contained in the structure. In addition, the free radical polymerizable double bonds, hydrophilic functional groups and hydrophobic groups in the molecular structure may contain multiple types.

[0115] As the reactive emulsifier, a commercially available surfactant can be used. The commercially available anionic surfactant is not particularly limited, and examples thereof include ADEKAREASOAP SE (manufactured by Asahidenka Kogyo Co., Ltd.), AQUALON HS, BC, KH (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), LATEMUL S (manufactured by Kao Corporation), Antox MS (manufactured by Nippon Emulsifier Co., Ltd.), ADEKAREASOAP SDX, PP (manufactured by Asahidenka Kogyo Co., Ltd.), HITENOL A (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), ELEMINOL RS (manufactured by Sanyo Chemical Industries, Ltd.), and Spinomar (manufactured by Toyo Soda Kogyo Co., Ltd.). The commercially available nonionic surfactant is not particularly limited, and examples thereof include AQUALON RN, NOIGEN N (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), and ADEKAREASOAP NE (manufactured by Asahidenka Kogyo Co., Ltd.).

[0116] These can be used alone or in combination of two or more.

[0117] The amount of the reactive emulsifier used is preferably in the range of 1 to 20 parts by mass relative to 100 parts by mass of the (b) hydrophilic copolymer calculated from the amount of the raw materials charged. If the amount of the reactive emulsifier is 1 part by mass or more, the image reproducibility of the obtained printing plate tends to be improved, and if it is 20 parts by mass or less, the printing durability of the obtained printing plate tends to be improved.

[0118] When the (b) hydrophilic copolymer is synthesized by emulsion polymerization, a non-reactive emulsifier may be used as necessary.

[0119] The non-reactive emulsifier is not limited to the following, and examples thereof include anionic surfactants such as fatty acid soaps, rosin acid soaps, sulfonates, sulfates, phosphates, polyphosphates, and sarcosyl esters; cationic surfactants such as nitrilized oil derivatives, oil derivatives, fatty acid derivatives, and α-olefin derivatives; and nonionic surfactants such as alcohol ethoxylates, alkylphenol ethoxylates, propoxylates, aliphatic alkanolamides, alkyl polyglycosides, polyoxyethylene sorbitan fatty acid esters, and oxyethylene propylene oxide block copolymers. These may be used alone or in combination of two or more.

[0120] Examples of the sulfonate include, but are not limited to, alkyl sulfonates, alkyl sulfates, alkyl sulfosuccinates, polyethylene oxide alkyl sulfates, sulfonated fats and oils, alkyl diphenyl ether disulfonates, α-olefin sulfonates, alkyl glyceryl ether sulfonates, and N-acylmethyl taurine salts.

[0121] Other examples of the non-reactive emulsifier include those described in "Surfactant Handbook" (Takahashi, Namba, Koike, Kobayashi: Engineering Publishing, 1972) .

[0122] The amount of the non-reactive emulsifier used is preferably less than 1 part by mass relative to 100 parts by mass of the (b) hydrophilic copolymer calculated from the amount of the raw materials charged. When the amount of the non-reactive emulsifier used is less than 1 part by mass, the obtained printing plate has an appropriate water swelling ratio, and a reduction in abrasion resistance during ink adhesion and a reduction in image reproducibility after moisture absorption can be prevented.

[0123] As the emulsion polymerization method of the hydrophilic copolymer (b), a predetermined amount of water, an emulsifier, and other additives are usually introduced into a reaction system adjusted to a temperature capable of polymerization, and a polymerization initiator, an unsaturated monomer, an emulsifier, a regulator, etc. are added to the reaction system in a batch operation or a continuous operation. In addition, it is also a commonly used method to introduce a predetermined amount of seed latex, a polymerization initiator, an unsaturated monomer, and other regulators into the reaction system in advance as needed.

[0124] Furthermore, by devising a method for adding unsaturated monomers, emulsifiers, other additives, and adjusters to the reaction system, it is also possible to change the layer structure of the synthesized hydrophilic copolymer particles in stages.

[0125] In this case, representative physical properties of each layer structure include hydrophilicity, glass transition temperature, molecular weight, crosslinking density, etc. In addition, there is no particular limitation on the number of stages of the layer structure.

[0126] (b) In the step of polymerizing the hydrophilic copolymer, a known chain transfer agent can be used.

[0127] As the chain transfer agent, a chain transfer agent containing sulfur element can be suitably used. As the chain transfer agent containing sulfur element, for example, alkyl mercaptan such as tert-dodecyl mercaptan and n-dodecyl mercaptan; thioalkanol such as mercaptoethanol and mercaptopropanol; thioalkylcarboxylic acid such as thioglycolic acid and thiopropionic acid; thioalkylcarboxylic acid alkyl esters such as octyl thioglycolate and octyl thiopropionate; thioethers such as dimethyl sulfide and diethyl sulfide can be listed, but not limited to the following.

[0128] Examples of other chain transfer agents include, but are not limited to, halogenated hydrocarbons such as terpinene, dipentene, terpinene, and carbon tetrachloride.

[0129] Among these chain transfer agents, alkanethiols are preferred from the viewpoints of having a high chain transfer rate and good balance in physical properties of the obtained polymer.

[0130] These chain transfer agents may be used alone or in combination of two or more.

[0131] These chain transfer agents are mixed with monomers and supplied to the reaction system, or added alone in a predetermined amount at a predetermined time. The amount of these chain transfer agents used is preferably 0.1 to 10% by mass based on the total amount of unsaturated monomers used in the polymerization of (b) the hydrophilic copolymer.

[0132] When the content is 0.1% by mass or more, the processability during mixing of the photosensitive resin composition is good, and when the content is 10% by mass or less, the molecular weight of the (b) hydrophilic copolymer can be made sufficient for practical use.

[0133] (b) During the polymerization of the hydrophilic copolymer, a polymerization inhibitor may be used as necessary.

[0134] A polymerization inhibitor refers to a compound that reduces the rate of free radical polymerization by being added to an emulsion polymerization system. More specifically, a polymerization inhibitor refers to a polymerization rate retardant, an inhibitor, a chain transfer agent with low free radical restart reactivity, and a monomer with low free radical restart reactivity. Polymerization inhibitors are generally used to adjust the polymerization rate and the physical properties of the latex. These polymerization inhibitors are added to the reaction system in batch operation or continuous operation. When a polymerization inhibitor is used, the strength of the latex coating is improved and the printing resistance is improved. The detailed reaction mechanism is unclear, but it is believed that the polymerization inhibitor is closely related to the three-dimensional structure of the polymer, and it is presumed that it has an effect on adjusting the physical properties of the latex coating.

[0135] The polymerization inhibitors are not limited to the following, and examples thereof include quinones such as o-benzoquinone, m-benzoquinone, or p-benzoquinone; nitro compounds such as nitrobenzene, o-dinitrobenzene, m-dinitrobenzene, or p-dinitrobenzene; amines such as diphenylamine; catechol derivatives such as tert-butylcatechol; 1,1-diphenylethylene, α-methylstyrene, 2,4-diphenyl-4-methyl-1-pentene, and other 1,1-disubstituted vinyl compounds; 2,4-diphenyl-4-methyl-2-pentene, cyclohexene, and other 1,2-disubstituted vinyl compounds; and the like. In addition, "POLYMER HANDBOOK 3 rd Compounds described as polymerization inhibitors or polymerization retarder in "Revised Chemistry of Polymer Synthesis (Otsu: Chemical Dojin, 1979)".

[0136] Among them, 2,4-diphenyl-4-methyl-1-pentene (α-methylstyrene dimer) is particularly preferred from the viewpoint of reactivity. These polymerization inhibitors may be used alone or in combination of two or more.

[0137] The amount of these polymerization inhibitors used is preferably 10% by mass or less based on the total amount of the unsaturated monomers used in the polymerization of the (b) hydrophilic copolymer. When the amount is 10% by mass or less, a practically sufficient polymerization rate tends to be obtained.

[0138] A radical polymerization initiator which is a preferred example of the polymerization initiator is an initiator which undergoes radical decomposition in the presence of heat or a reducing substance to initiate addition polymerization of monomers, and both inorganic initiators and organic initiators can be used.

[0139] The free radical polymerization initiator is not limited to the following, and examples thereof include water-soluble or oil-soluble peroxodisulfate salts, peroxides, azobis compounds, and the like. Specifically, examples thereof include potassium peroxodisulfate, sodium peroxodisulfate, ammonium peroxodisulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, 2,2-azobisbutyronitrile, and cumene hydroperoxide.

[0140] As the radical polymerization initiator, POLYMER HANDBOOK (3 rd The compounds described in J. Brandrup and E. H. Immergut, John Willy & Sons (1989).

[0141] Alternatively, a so-called redox polymerization method may be employed in which a reducing agent such as sodium bisulfite, ascorbic acid or its salt, isoascorbic acid or its salt, hydrosulfite, etc. is used in combination with a polymerization initiator.

[0142] Among them, peroxodisulfate salts are suitable as the polymerization initiator.

[0143] The amount of the polymerization initiator used is usually within the range of 0.1 to 5.0% by mass, preferably within the range of 0.2 to 3.0% by mass, based on the total amount of the unsaturated monomers used for polymerization of the (b) hydrophilic copolymer.

[0144] When the amount of the polymerization initiator used is 0.1 mass % or more, high stability can be obtained during the synthesis of the (b) hydrophilic copolymer, and when the amount of the polymerization initiator used is 5.0 mass % or less, the moisture absorption of the photosensitive resin composition can be suppressed within a practically good range.

[0145] (b) When synthesizing the hydrophilic copolymer, various polymerization regulators may be added as necessary.

[0146] The pH adjuster is not limited to the following, and for example, a pH adjuster such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, sodium hydrogen carbonate, sodium carbonate, or disodium hydrogen phosphate may be added as a polymerization adjuster.

[0147] In addition, various chelating agents such as sodium ethylenediaminetetraacetate may be added as polymerization regulators.

[0148] Furthermore, as other additives, various additives such as alkali-sensitive latex, detackifiers such as hexametaphosphoric acid, water-soluble polymers such as polyvinyl alcohol and carboxymethyl cellulose, thickeners, various antioxidants, ultraviolet absorbers, preservatives, bactericides, defoaming agents, dispersants such as sodium polyacrylate, water-resisting agents, metal oxides such as zinc white, isocyanate compounds, epoxy compounds and other cross-linking agents, lubricants, water-retaining agents, etc. can be added.

[0149] There is no particular limitation on the method of adding these additives, and they may be added during or after the synthesis of the (b) hydrophilic copolymer.

[0150] The polymerization temperature when emulsion polymerizing the (b) hydrophilic copolymer is usually selected within the range of 60 to 120°C.

[0151] In addition, polymerization can also be performed at a lower temperature by the above-mentioned redox polymerization method, etc. Furthermore, as a redox catalyst, a metal catalyst such as divalent iron ions, trivalent iron ions, copper ions, etc. may coexist.

[0152] The (b) hydrophilic copolymer is preferably in a particulate form, and its average particle size is preferably 500 nm or less, more preferably 100 nm or less. When the average particle size is 500 nm or less, good water-based developability is obtained in the obtained printing original plate.

[0153] The toluene gel fraction of the (b) hydrophilic copolymer is preferably 60% to 99%. If the gel fraction is 60% or more, there is a tendency that a practically sufficient strength is obtained in the obtained printing plate.

[0154] When the gel fraction is 99% or less, the miscibility of the (b) hydrophilic copolymer and the (a) thermoplastic elastomer tends to be good.

[0155] Here, the toluene gel fraction refers to a process in which an appropriate amount of a dispersion of about 30% by weight of the (b) hydrophilic copolymer is dropped onto a Teflon (registered trademark) sheet, and the mixture is dried at 130°C for 30 minutes. 0.5 g of the (b) hydrophilic copolymer is taken out and immersed in 30 mL of toluene at 25°C. After being shaken for 3 hours using an oscillator, the mixture is filtered using a 320SUS mesh, and the mass of the non-passing component after drying at 130°C for 1 hour is divided by 0.5 (g) to obtain the mass fraction (%).

[0156] When the photosensitive resin composition layer is developed in an aqueous developer, the content of the hydrophilic copolymer (b) is preferably 10% to 70% by mass when the total amount of the photosensitive resin composition is 100% by mass, from the viewpoint of developability during printing plate production. The content of the hydrophilic copolymer (b) is more preferably 15% to 60% by mass, and further preferably 20% to 50% by mass.

[0157] <(c) Photopolymerizable monomer>

[0158] The photopolymerizable monomer (c) is not limited to the following, and examples thereof include esters of acrylic acid, methacrylic acid, fumaric acid, maleic acid, etc.; derivatives of acrylamide and methacrylamide; allyl esters, styrene and its derivatives; and N-substituted maleimide compounds.

[0159] The photopolymerizable monomer (c) is not limited to the following, and examples thereof include diacrylates and dimethacrylates of alkane diols such as 1,6-hexanediol and 1,9-nonanediol; or diacrylates and dimethacrylates of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, polyethylene glycol, butanediol, and dicyclopentadienyl; trimethylolpropane tri(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, isobornyl (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, pentaerythritol tetramethacrylate. (Meth)acrylate, N,N'-hexamethylenebisacrylamide and methacrylamide, styrene, vinyltoluene, divinylbenzene, diallyl phthalate, triallyl cyanurate, diethyl fumarate, dibutyl fumarate, dioctyl fumarate, distearyl fumarate, butyl octyl fumarate, diphenyl fumarate, dibenzyl fumarate, dibutyl maleate, dioctyl maleate, bis(3-phenylpropyl) fumarate, dilauryl fumarate, di(behenyl) fumarate, N-laurylmaleimide, etc.

[0160] These can be used individually by 1 type or in combination of 2 or more types.

[0161] From the viewpoint of further improving the defect resistance of the convex portion of the printing plate, it is preferred that the photosensitive resin composition contain 2.0 mass % or more of a monomer having 2 mol of a methacrylate group as the (c) photopolymerizable monomer.

[0162] The content of the photopolymerizable monomer (c) in the photosensitive resin composition layer is preferably 1% to 25% by mass when the total amount of the photosensitive resin composition is 100% by mass from the viewpoint of obtaining bright printing. The content of the photopolymerizable monomer (c) is more preferably 5% to 20% by mass, and further preferably 8% to 15% by mass.

[0163] ((d) Photopolymerization initiator)

[0164] (d) The photopolymerization initiator refers to a compound that absorbs light energy and generates radicals. Various known photopolymerization initiators can be used, and various organic carbonyl compounds, particularly aromatic carbonyl compounds, are preferred.

[0165] (d) The photopolymerization initiator is not limited to the following, and examples thereof include thioxanthones such as benzophenone, 4,4-bis(diethylamino)benzophenone, tert-butyl anthraquinone, 2-ethyl anthraquinone, 2,4-diethyl thioxanthone, isopropyl thioxanthone, and 2,4-dichlorothioxanthone; diethoxyacetophenone, 2,2-dimethoxyphenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyl dimethyl acetal, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino (4-thiomethylphenyl) propane-1-one, 2-benzyl- Acetophenones such as 2-dimethylamino-1-(4-morpholinophenyl)-butanone; benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; acyl phosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; methyl benzoyl formate; 1,7-bisacridinylheptane; 9-phenylacridine; 2,6-di-tert-butyl-p-cresol; etc.

[0166] These can be used alone or in combination of two or more.

[0167] The content of the photopolymerization initiator (d) in the photosensitive resin composition layer is preferably 0.1% to 10.0% by mass when the total amount of the photosensitive resin composition is 100% by mass, from the viewpoint of improving the plate formability during platemaking and obtaining bright printing. The content of the photopolymerization initiator (d) is more preferably 1.0% to 8.0% by mass, and further preferably 1.5% to 5.0% by mass.

[0168] In addition, as the (d) photopolymerization initiator, a disintegration type photopolymerization initiator and a hydrogen abstraction type photopolymerization initiator may be used in combination. From the viewpoint of high image reproducibility and wear resistance of the printing plate, the amount of the hydrogen abstraction type photopolymerization initiator in the photosensitive resin composition is preferably 1.0% by mass or less, more preferably 0.5% by mass or less.

[0169] (Middle layer)

[0170] The flexographic printing plate of the present embodiment has an intermediate layer between the photosensitive resin composition layer and the infrared ablation layer described later.

[0171] In order to produce a high-definition printed material with a highlight area, it is necessary to form a tiny dot with a flat portion at the top of the dot having a diameter of 10 to 20 μm and a relief depth of 100 μm or more. To achieve such a tiny dot, the intermediate layer preferably has oxygen barrier properties.

[0172] When the photosensitive resin composition layer is cured by ultraviolet irradiation, the curing is carried out by free radical polymerization. If oxygen coexists during polymerization, the free radical generating compound reacts with oxygen, and the polymerization reaction is inhibited. If the polymerization reaction is inhibited and an unreacted portion remains in the photosensitive resin composition layer, the final pattern formed becomes a shape with a curved portion at the top. In contrast, if the coexisting amount of oxygen is reduced during ultraviolet curing, the polymerization reaction is not easily inhibited, and the final pattern formed becomes a shape with a flat portion at the top. Therefore, when you want to make a pattern with a flat portion at the top, it is effective to reduce the oxygen in contact with the photosensitive resin composition layer by having an intermediate layer with oxygen barrier ability.

[0173] In addition, the intermediate layer also has a function of protecting the infrared ablation layer described later.

[0174] In the conventional manufacturing process of flexographic printing plates, when the infrared ablation layer is fed as a film, it may physically fail due to contact with a roller or friction with a protective film due to tight winding during film roll transport, thereby generating pinholes.

[0175] In addition, when the photosensitive resin composition layer and the infrared ablation layer are laminated by a method in which the photosensitive resin composition layer is extruded and coated on the infrared ablation layer, pinholes may be generated due to friction generated when the heated and molten photosensitive resin composition flows on the infrared ablation layer.

[0176] In order to prevent the generation of such pinholes in the infrared ablation layer, the intermediate layer constituting the flexographic printing original plate of the present embodiment needs to have physical strength and heat resistance.

[0177] As described above, in order to produce high-definition printed materials with highlight areas, it is necessary to form a flat portion at the top of the dot with a tiny dot of 10 to 20 μm in diameter. Therefore, if there are pinholes larger than 20 μm in the infrared ablation layer and a mask image for forming tiny dots overlaps its periphery, poor dot formation may occur and a high-definition flexible printing plate with highlight areas cannot be produced.

[0178] Furthermore, from the viewpoint of simplicity of the production process of the flexographic printing plate, the intermediate layer is preferably washed with the same washing liquid as that of the infrared ablative layer and / or the photosensitive resin composition layer.

[0179] From this viewpoint, the intermediate layer is preferably water-soluble or alkali-soluble.

[0180] When the intermediate layer has high washability, the time required for the washing step can be shortened, workability can be improved, and the photosensitive resin composition layer located under the intermediate layer can be easily developed.

[0181] In the flexographic printing plate of this embodiment, the intermediate layer contains a hydrophilic resin (A) and an inorganic layered compound (B), thereby having oxygen barrier properties, excellent physical strength and heat resistance, improved pinhole resistance, and improved washability of the intermediate layer.

[0182] Although it is not clarified in detail, the present inventors presume it as follows.

[0183] Inorganic layered compound (B) is formed by dispersing clay minerals through layered exfoliation in aqueous solution or by dispersing crystalline inorganic fine particles in water. Clay minerals have silanol groups (SiOH) on their surfaces, which can be bonded with hydroxyl groups, etc. Furthermore, clay minerals through layered exfoliation have negative charges on the surface, and therefore can also form ionic bonds with cations such as quaternary ammonium ions. By forming a cross-linked structure between the inorganic layered compound (B) and the hydrophilic resin (A), the strength of the intermediate layer is improved, and the physical strength and heat resistance are improved. Similarly, when inorganic compounds such as aluminum hydroxide, barium sulfate, potassium titanate are contained in the inorganic layered compound (B), their surface functional groups can also be bonded with hydroxyl groups, etc. In addition, water-dispersible particles have negative charges on the surface, and therefore can form ionic bonds with cations such as quaternary ammonium ions, etc.

[0184] Furthermore, in the washing step, the inorganic layered compound (B) and the hydrophilic resin (A) form a crosslinked structure, whereby the intermediate layer is not dissolved but removed by film stripping, thereby accelerating the dissolution rate of the hydrophilic resin (B) in the washing liquid and improving the washing properties.

[0185] For the middle layer, the more the content of the inorganic layered compound (B) is, the more oxygen barrier properties, pinhole resistance and washability are improved. On the other hand, the film-coating property deteriorates, and there is a tendency to be difficult to obtain a film with uniform film thickness. If their balance is taken into account, the content of the inorganic layered compound (B) in the middle layer is preferably 0.1 mass parts or more and 20 mass parts or less, more preferably 1 mass parts or more, and further preferably 1.5 mass parts or more relative to 100 mass parts of the hydrophilic resin (A). In addition, it is more preferably 10 mass parts or less, and further preferably 8 mass parts or less.

[0186] The thicker the intermediate layer, the better the oxygen barrier effect, physical strength and heat resistance. On the other hand, the washability decreases.

[0187] Taking the balance into consideration, the thickness of the intermediate layer is 2 μm or more and 30 μm or less, preferably 2.5 μm or more, more preferably 3 μm or more. Also, preferably 15 μm or less, more preferably 8 μm or less. The thickness of the intermediate layer can be measured by the method described in the examples described below.

[0188] Hereinafter, each component contained in the intermediate layer will be described in detail.

[0189] <Hydrophilic resin (A)>

[0190] Hydrophilic resins generally refer to polymers that have water-soluble polar groups and are soluble in water.

[0191] As water-soluble polar groups, amino groups, imino groups, tertiary amine groups, quaternary ammonium salt groups, hydrazide groups, carboxyl groups, sulfonyl groups, sulfate groups, phosphate groups, ether groups, hydroxyl groups, amide groups, etc. can be listed. In particular, the hydrophilic resin (A) in the intermediate layer of the flexographic printing original plate of the present embodiment preferably contains a functional group that can be covalently bonded and / or ionically bonded to a clay mineral. As such functional groups, specifically, hydroxyl groups that can be siloxane-bonded to a clay mineral, or amino groups, imino groups, tertiary amine groups, and quaternary ammonium salt groups that can be ionically bonded to a clay mineral can be listed.

[0192] The above functional groups can selectively react when the inorganic layered compound (B) described later is a layered exfoliated clay mineral. That is, there are silanol groups (SiOH) on the surface of the layered exfoliated clay mineral, so it is effective and easy to form a siloxane bond (Si-O-Si) for bonding. Furthermore, the layered exfoliated clay mineral has a negative charge on the surface, so it is easy to form an ionic bond with a quaternary ammonium ion (cation).

[0193] Specific examples of the hydrophilic resin (A) include water-soluble poly(ethylene-vinyl alcohol) copolymers, polyvinyl alcohol, partially saponified polyvinyl acetate, partially saponified poly(ethylene oxide vinyl acetate) graft copolymers, polyvinyl butyral, polyvinyl pyrrolidone, polyurethane, polyester, polyether, cellulose, polyamide, and water-soluble phenols.

[0194] These can be used alone or in combination of two or more.

[0195] <Inorganic layered compound (B)>

[0196] The "inorganic layered compound" refers to an inorganic compound in which unit crystal layers overlap to form a layered particle.

[0197] The inorganic layered compound (B) is preferably a compound that swells and / or dissolves in water, and examples thereof include clay compounds that swell in water. In addition, inorganic layered compounds containing aluminum hydroxide, barium sulfate, and potassium titanate dispersed in water may be mentioned. Among these compounds, clay compounds that swell in water and inorganic layered compounds containing aluminum hydroxide dispersed in water are particularly preferred.

[0198] This clay compound is usually Si 4+ For O 2-Coordinate to form a tetrahedral structure layer, and Al 3+ Mg 2+ , Fe 2 + , Fe 3+ For O 2- and OH - The layers that coordinate to form an octahedral structure are bonded and stacked in a 1:1 or 2:1 ratio to form a layered structure. Such clay compounds may be natural compounds or synthetic compounds.

[0199] Aluminum hydroxide dispersed in water is formed into fine particles and dispersed in a solution. It can be a compound used in a sol state in which a metal oxide or a metal hydroxide is dispersed by hydrolyzing and dehydrating and polycondensing various aluminum hydroxides in a hydrated form (amorphous aluminum hydroxide, gibbsite, magnesia phosphate, boehmite, diaspore) in a solution, or it can be obtained by dispersing aluminum hydroxide produced by a hydrothermal synthesis method with water under high temperature and high pressure conditions in water.

[0200] From the viewpoint of compatibility with the hydrophilic resin (A) and the aforementioned washability, the inorganic layered compound (B) is preferably a water-swellable clay mineral that swells in water or dissociates in layers, and more preferably is dispersed in water in a single layer or multiple layers.

[0201] Preferred clay minerals include, for example, layered silicate minerals such as kaolinite, dickite, halloysite, talc, pyrophyllite, saponite, lithium magnesium silicate, montmorillonite, beidellite, vermiculite, mica, and sodium mica.

[0202] In particular, mica has a higher aspect ratio than other inorganic layered compounds, and therefore exhibits a more effective labyrinth effect. The oxygen barrier property of the intermediate layer formed by combining with the hydrophilic resin (A) is particularly improved. Therefore, it is preferred as the inorganic layered compound (B). Since the average particle size dispersion is narrow and the washability of the intermediate film in which the inorganic layered compound is uniformly dispersed is improved, water-swellable synthetic mica is more preferred.

[0203] The size of the inorganic layered compound (B) is preferably such that the inorganic layered compound (B) is uniformly arranged in the intermediate layer formed together with the hydrophilic resin (A) used in combination, the labyrinth effect is more effectively exerted, and the oxygen barrier property of the intermediate layer is particularly high. From the above viewpoints, the inorganic layered compound (B) preferably has an average particle size of 10 μm or less and a thickness of 500 nm or less, and more preferably has an average particle size of 10 μm or less and a thickness of 100 nm or less.

[0204] When the average particle size is 1 μm or more, sufficient oxygen barrier properties can be exhibited in the intermediate layer. When the average particle size is 10 μm or less, the occurrence of uneven appearance can be prevented.

[0205] When the thickness is 10 nm or more, the particle shape can be maintained and is suitable for practical use. When the thickness is 500 nm or less, uniform coating can be achieved and sufficient oxygen barrier properties can be exhibited.

[0206] Examples of commercially available inorganic layered compounds (B) include Micro Mica (synthetic mica), Somasif (registered trademark of Katakura & Co-op Agri Corporation, synthetic mica), Kunipia (registered trademark of KUNIMINE INDUSTRIES CO., LTD., montmorillonite), and Sumecton (registered trademark of KUNIMINE INDUSTRIES CO., LTD.) SA (synthetic soapstone) manufactured by KUNIMINE INDUSTRIES CO., LTD.; BEN-GEL (registered trademark of HOJUN CO., LTD., purified natural bentonite) manufactured by HOJUN CO., LTD.; and alumina sols F-1000, F-3000, 5N, and Kinsei Matec manufactured by Kawaken Fine Chemicals Co., Ltd. Plate-shaped alumina powder Serath 00610, 02025, 02050, 05025, 05070, 07070, 10030 manufactured by KOGASA CO., LTD., Tismo D and Tismo N manufactured by Otsuka Chemical Co., Ltd., etc.

[0207] <Water-dispersible latex (C)>

[0208] In the flexographic printing plate of the present embodiment, the intermediate layer preferably further contains a water-dispersible latex (C) from the viewpoint of improving the water developability of the intermediate layer.

[0209] As the water-dispersible latex (C), any water-dispersible latex polymers can be used as long as they are uniformly mixed with the hydrophilic resin (A). Examples of the water-dispersible latex polymers include, but are not limited to, polybutadiene latex, natural rubber latex, styrene-butadiene copolymer latex, acrylonitrile-butadiene copolymer latex, polychloroprene latex, polyisoprene latex, polyurethane latex, methyl methacrylate-butadiene copolymer latex, vinylpyridine polymer latex, butyl polymer latex, polysulfide rubber polymer latex, acrylate polymer latex, and latex copolymers obtained by copolymerizing these polymers with other components such as acrylic acid and methacrylic acid.

[0210] In particular, a water-soluble or water-dispersible latex copolymer having a hydrophilic group such as a carboxyl group, an amino group, a hydroxyl group, a phosphoric acid group, a sulfonic acid group, or a polar group such as a salt thereof is preferred.

[0211] In the production process of a flexographic printing plate using the flexographic printing original plate of the present embodiment, from the viewpoint of obtaining high washability, the latex polymer having the polar group is preferably a butadiene latex containing a carboxyl group or a hydroxyl group.

[0212] These latex polymers having a polar group may be used alone or in combination of two or more.

[0213] The content ratio of the water-dispersible latex (C) in the intermediate layer of the flexographic printing original plate of this embodiment is preferably 10 mass % or more, more preferably 20 mass % or more, and further preferably 25 mass % or more relative to the total amount of the intermediate layer from the viewpoint of washability in the manufacturing process of the printing plate.

[0214] Furthermore, it is preferably 80% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0215] When the content of the water-dispersible latex (C) in the intermediate layer is 10% by mass or more, sufficient washing properties can be obtained, and when the content is 80% by mass or less, sufficient film strength can be obtained, and a flexographic printing plate with low tack can be obtained.

[0216] The content of the water-dispersible latex (C) is preferably 5 parts by mass or more and 45 parts by mass or less per 100 parts by mass of the hydrophilic resin (A) in the intermediate layer. From the viewpoint of obtaining sufficient cleaning properties, it is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more.

[0217] From the viewpoint of exhibiting sufficient oxygen barrier properties and improving the reproducibility of printed matter of small dots, the content is preferably 45 parts by mass or less, and more preferably 20 parts by mass or less.

[0218] The gel fraction of the intermediate layer is preferably 10% or more and 90% or less. The gel fraction can be calculated by the following formula.

[0219] Gel fraction (%) = (mass of the intermediate layer after being immersed in pure water at room temperature for 72 hours and then dried at 50°C for 3 hours / mass of the intermediate layer before being immersed in pure water) × 100

[0220] The gel fraction is preferably 10% or more, more preferably 30% or more, more preferably 60% or more, and further preferably 70% or more from the viewpoint of water resistance of the intermediate layer, and is preferably 90% or less, more preferably 80% or less, and further preferably 70% or less from the viewpoint of washability.

[0221] The gel fraction can be measured by the method described in Examples below.

[0222] The gel fraction is an index of the degree of crosslinking of the intermediate layer components. If the value increases, the water resistance is improved, and there is a tendency for the number of defects to decrease in the pinhole evaluation during high humidity storage. If the value of the gel fraction decreases, the water resistance decreases, and there is a tendency for the number of defects to increase in the pinhole evaluation during high humidity storage. In addition, the gel fraction can be controlled by adjusting the aspect ratio of the inorganic layered compound (B), the number of functional groups of the hydrophilic resin (A), and the glass transition temperature (Tg) of the water-dispersed latex (C). There is a tendency that the higher the value of the aspect ratio, the number of functional groups of the hydrophilic resin (A), and the glass transition temperature of the water-dispersed latex (C), the higher the value of the gel fraction.

[0223] In addition, from the viewpoint of improving the uniformity of the film thickness during coating of the intermediate layer, the intermediate layer may contain a siloxane compound or a surfactant.

[0224] <Siloxane compounds>

[0225] The intermediate layer can be formed, for example, by coating a material for forming the intermediate layer on the infrared ablation layer. In order to uniformly coat the intermediate layer on the infrared ablation layer, the intermediate layer preferably contains a siloxane compound or a surfactant from the viewpoint of controlling the surface energy.

[0226] As the siloxane compound, there is no particular limitation on the molecular structure, and compounds having polyalkylsiloxanes such as polydimethylsiloxane and polydiethylsiloxane in the main chain can be cited as preferred compounds. In addition, compounds having a polysiloxane structure in part of the molecule can be used. Furthermore, compounds having a specific organic group introduced into the polysiloxane structure can also be used. Specifically, compounds having an organic group introduced into the side chain of polysiloxane, compounds having an organic group introduced into both ends of polysiloxane, compounds having an organic group introduced into one end of polysiloxane, compounds having an organic group introduced into both the side chain and the end of polysiloxane, etc. can be used.

[0227] From the viewpoint of ensuring the adhesiveness between the intermediate layer and the photosensitive resin composition layer, it is preferred to use a siloxane compound into which an organic group has been introduced.

[0228] Examples of the organic group introduced into the polysiloxane structure include, but are not limited to, amino, carboxyl, methylol, aryl, alkyl, alkoxycarbonyl, alkoxy, linear or branched alkyl substituted with at least one aryl group, and polyoxyalkylene (hereinafter also referred to as polyether group).

[0229] The siloxane compound is not limited to the following, and various organic group-substituted silicone oils manufactured by Shin-Etsu Chemical Co., Ltd., Wacker Asahikasei Silicone Co., Ltd., GE Toshiba Silicones Co., Ltd., and Dow Corning Toray Silicone Company can be used, for example.

[0230] The siloxane compound preferably contains 0.01 mass % to 1.0 mass % when the total amount of materials forming the intermediate layer is 100 mass %, more preferably 0.05 mass % to 0.5 mass %, and further preferably 0.05 mass % to 0.3 mass %.

[0231] <Surfactant>

[0232] Examples of the surfactant include anionic surfactants, ionic surfactants, nonionic surfactants, anionic reactive surfactants, and nonionic reactive surfactants.

[0233] Examples of the surfactant include, but are not limited to, sodium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyethylene branched decyl ether sulfate, ammonium polyoxyethylene isodecyl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, sodium polyoxyethylene alkyl (C8 to C20) ether sulfate, ammonium polyoxyethylene oleyl cetyl ether sulfate, sodium polyoxyethylene oleyl cetyl ether sulfate, polyoxyethylene tridecyl ether phosphate, polyoxyethylene alkyl (C2 to C16) ether phosphate, polyoxyethylene Anionic surfactants such as ethylene alkyl (C2-C16) ether phosphate ester monoethanolamine salt, alkyl (C2-C16) phosphate sodium, alkyl (C2-C16) phosphate ester monoethanolamine salt, disodium lauryl sulfosuccinate, disodium polyoxyethylene lauryl sulfosuccinate, disodium polyoxyethylene alkyl (C2-C20) sulfosuccinate, sodium linear alkylbenzene sulfonate, linear alkylbenzene sulfonic acid, sodium α-olefin sulfonate, phenol sulfonic acid, sodium dioctyl sulfosuccinate, sodium lauryl sulfate, and higher fatty acid potassium salts;

[0234] Ionic surfactants such as alkyl (C8-C20) trimethylammonium chloride, alkyl (C8-C20) dimethylethylammonium chloride, didecyldimethylammonium chloride, lauryldimethylbenzylammonium chloride, stearyldimethylhydroxyethylammonium p-toluenesulfonate, stearyldimethylaminopropylamide, tributylbenzylammonium chloride, lauryldimethylaminoacetic acid betaine, lauric acid amide propyl betaine, coconut oil fatty acid amide propyl betaine, caprylic acid amide propyl betaine, and lauryldimethylamine oxide;

[0235] Polyoxyalkylene tridecyl ether, polyoxyethylene isodecyl ether, polyoxyalkylene lauryl ether, polyoxyalkylene alkyl ether, mixture of polyoxyalkylene ether and polyether polyol, polyether polyol, polyoxyethylene sulfonated phenyl ether, polyoxyethylene naphthyl ether, phenoxyethanol, polyoxyethylene phenyl ether, polyoxyethylene polyoxypropylene glycol, polyoxyethylene lauryl ether, polyoxyethylene oleyl cetyl ether, polyoxyethylene oleate, polyoxyethylene distearate, polyoxyethylene glyceryl isostearate, polyoxyethylene hydrogenated castor oil, coconut oil fatty acid diethanolamide, polyoxyethylene alkylamine, sorbitan trioleate, Nonionic surfactants such as sorbitan sesquioleate, sorbitan monooleate, sorbitan monococoate, sorbitan monodecanoate, polyoxyethylene sorbitan monococoate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, octyl polyglycoside, butyl polyglycoside, sucrose benzoate, sucrose acetate, and sucrose fatty acid esters; anionic reactive surfactants such as polyoxyethylene-1-(allyloxymethyl) alkyl ether ammonium sulfate and polyoxyethylene nonylpropenylphenyl ether ammonium sulfate; nonionic reactive surfactants such as polyoxyethylene nonylpropenylphenyl ether, etc.

[0236] The above-mentioned surfactants may be used alone or in combination of two or more.

[0237] In addition to the intermediate layer, the surfactant may also be added to other layers, such as a photosensitive resin composition layer, and when the total amount of the material of the layer to which it is added is set to 100% by mass, it is preferably contained in a range of 0.1% by mass to 5.0% by mass, more preferably in a range of 0.5% by mass to 3.0% by mass, and further preferably in a range of 0.5% by mass to 2.0% by mass.

[0238] By containing 0.1% by mass or more of the surfactant, the washing speed during development after exposure can be improved. In addition, by containing 5.0% by mass or less of the surfactant, there is a tendency that the swelling of the flexographic printing original plate can be suppressed.

[0239] (Infrared ablation layer)

[0240] The flexographic printing plate of the present embodiment has an infrared ablative layer on the photosensitive resin composition layer via an intermediate layer.

[0241] The infrared ablation layer can be processed by infrared rays and plays a role of a mask image when the photosensitive resin composition layer is exposed and cured. When the unexposed part of the photosensitive resin composition layer is washed out after the exposure, the infrared ablation layer is also removed at the same time.

[0242] The infrared ablation layer is preferably composed of a binder polymer and an infrared sensitive substance.

[0243] Examples of the binder polymer include polyamide, polyester, and a copolymer containing a monovinyl-substituted aromatic hydrocarbon and a conjugated diene.

[0244] In particular, a copolymer containing a monovinyl-substituted aromatic hydrocarbon such as styrene, α-methylstyrene, and vinyltoluene, and a conjugated diene such as 1,3-butadiene and isoprene is preferred.

[0245] When the infrared ablation layer is constituted using the aforementioned binder polymer, the affinity with the photosensitive composition resin layer is high and the adhesion becomes good.

[0246] When polyester is used as the binder polymer, the number average molecular weight is preferably 300 or more and 10,000 or less.

[0247] Furthermore, the polyester is not limited to the following, and suitable examples include polyesters synthesized from alkanediol and adipic acid, polyesters synthesized from alkanediol and phthalic acid, polycaprolactone, and combinations of two or more of these polyesters.

[0248] Furthermore, the polyester may contain various functional groups such as an amino group, a nitro group, a sulfonic acid group, and a halogen group within a range that does not impair compatibility with other binder polymers, infrared sensitive materials, and non-infrared radiation shielding materials.

[0249] The infrared sensitive substance is not limited to the following, and for example, a simple substance or a compound having strong absorption in the range of 750 to 2000 nm is preferably used.

[0250] Examples of the infrared sensitive substance include, but are not limited to, inorganic pigments such as carbon black, graphite, copper chromite, and chromium oxide; pigments such as polyphthalocyanine compounds, cyanine pigments, and metal thiolate pigments; and the like.

[0251] These infrared sensitive substances are added in a range that provides sensitivity that enables ablation by the laser beam used, and are generally effective when added in an amount of 10 to 80% by mass.

[0252] Infrared sensitive substances can be substances that reflect or absorb ultraviolet radiation. Ultraviolet radiation absorbers, carbon black, graphite, etc. are good examples thereof, and the amount added is set so as to achieve a desired optical density. It is usually preferably added so as to form an optical density of 2 or more, preferably 3 or more.

[0253] [Method for producing flexographic printing plate]

[0254] The flexographic printing plate can be produced by laminating a photosensitive resin composition layer, an intermediate layer, and an infrared ablative layer on a support.

[0255] The method for producing the flexographic printing plate of the present embodiment is not particularly limited, and various methods may be used. Specifically, the following methods may be mentioned.

[0256] First, the raw materials of the photosensitive resin composition serving as the material of the photosensitive resin composition layer are dissolved and mixed in a suitable solvent, such as chloroform, tetrachloroethylene, methyl ethyl ketone, toluene and the like, and then cast in a mold frame to evaporate the solvent, thereby forming a plate-like shape; without using a solvent, a method in which after kneading with a kneader, an open mill or a screw extruder, the photosensitive resin composition layer is formed into a desired thickness by a calender roll, pressurization, etc., and the photosensitive resin composition layer is laminated to a support body, thereby obtaining a laminate of the support body and the photosensitive resin composition layer.

[0257] Next, an intermediate layer and an infrared ablative layer are formed on the photosensitive resin composition layer.

[0258] In order to arrange the intermediate layer and the infrared ablation layer on the surface of the photosensitive resin composition layer, for example, the components constituting the intermediate layer and the components constituting the infrared ablation layer are dispersed or dissolved in a suitable solvent by forced stirring or ultrasonic stirring using a stirring blade, or are dispersed or dissolved in a suitable solvent after preliminary kneading using an extruder or a kneader, thereby obtaining a predetermined dispersion or solvent, and then the dispersion or solution is directly applied to the photosensitive resin composition layer, thereby forming the intermediate layer and the infrared ablation layer.

[0259] In addition, a cover sheet made of, for example, polyester, polypropylene, etc. may be provided on the infrared ablation layer.

[0260] As another method, a material constituting an infrared ablation layer is coated on a specified covering sheet to obtain a film having an infrared ablation layer, and then a material constituting an intermediate layer is coated on the infrared ablation layer to obtain a covering film in which the infrared ablation layer and the intermediate layer are stacked on the covering sheet. Then, the covering film is laminated or press-bonded to the photosensitive resin composition layer-forming surface side of the stack of a support and a photosensitive resin composition layer, thereby forming an intermediate layer and an infrared ablation layer on the photosensitive resin composition layer.

[0261] The cover film or support is usually brought into close contact with the photosensitive resin composition layer by roll lamination after the sheet of the photosensitive resin composition layer is formed. If heating and pressurization are applied after lamination, a flexographic printing plate with further improved thickness accuracy can be obtained.

[0262] [Method for producing flexographic printing plate]

[0263] As a method of making a flexographic printing plate from a flexographic printing original plate, for example, the following method can be mentioned.

[0264] First, ultraviolet light exposure (back exposure) is applied to the entire surface through the support of the flexographic printing plate to cure the photosensitive resin composition layer to form a thin uniform cured layer.

[0265] Next, the infrared ablation layer on the photosensitive resin composition layer is laser drawn, that is, laser ablated to produce a negative pattern, and then the surface of the photosensitive resin composition layer is image-exposed (relief exposure) directly from above the infrared ablation layer having the negative pattern formed thereon.

[0266] Then, the unexposed portion is removed by washing it with a solvent-based developer or an aqueous developer, or by bringing the unexposed portion heated to 40° C. to 200° C. into contact with an absorbing layer capable of absorbing light to remove the absorbing layer.

[0267] Furthermore, by post-processing exposure, a flexographic printing plate is obtained.

[0268] Exposure from the infrared ablation layer side (relief exposure) and exposure from the support film side (back exposure) can be performed either first or simultaneously. Examples of the exposure light source include high pressure mercury lamps, ultraviolet fluorescent lamps, carbon arc lamps, and xenon lamps.

[0269] Infrared laser can be used for laser drawing, and the infrared laser is preferably an infrared laser with a wavelength of 750 to 2000 nm. The infrared laser with this wavelength is usually a semiconductor laser with a wavelength of 750 to 880 nm or a Nd-YAG laser with a wavelength of 1060 nm.

[0270] When the unexposed portion of the photosensitive resin composition layer is developed using a solvent-based developer, suitable examples of the developer include esters such as heptyl acetate and 3-methoxybutyl acetate; hydrocarbons such as petroleum fractions, toluene, and decalin; a developer prepared by mixing alcohols such as propanol, butanol, and pentanol in a chlorinated organic solvent such as tetrachloroethylene; water; ethers such as polyoxyalkylene alkyl ethers; and the like.

[0271] The unexposed portion can be washed out by spraying with a nozzle and / or by brushing with a brush.

[0272] When the unexposed portion of the photosensitive resin composition layer is developed using an aqueous developer, the aqueous developer is a developer containing water as a main component, and may be water itself, for example, a developer obtained by mixing nonionic, anionic or other surfactants, a pH adjuster, and a washing accelerator in water.

[0273] Examples of the nonionic surfactant include, but are not limited to, polyoxyalkylene alkyl or alkenyl ethers, polyoxyalkylene alkyl or alkenyl phenyl ethers, polyoxyalkylene alkyl or alkenyl amines, polyoxyalkylene alkyl or alkenyl amides, and ethylene oxide / propylene oxide block adducts.

[0274] Examples of the anionic surfactant include, but are not limited to, linear alkylbenzene sulfonates having an alkyl group with an average carbon number of 8 to 16, α-olefin sulfonates having an average carbon number of 10 to 20, dialkyl sulfosuccinates having an alkyl or alkenyl group with a carbon number of 4 to 10, sulfonates of fatty acid lower alkyl esters, alkyl sulfates having an average carbon number of 10 to 20, alkyl ether sulfates to which an average of 0.5 to 8 mol of ethylene oxide is added to a linear or branched alkyl or alkenyl group having an average carbon number of 10 to 20, and saturated or unsaturated fatty acid salts having an average carbon number of 10 to 22.

[0275] In addition, examples of pH adjusters include, but are not limited to, sodium borate, sodium carbonate, sodium silicate, sodium metasilicate, sodium succinate, sodium acetate, etc. Among the above, sodium silicate is preferred from the viewpoint of being easily soluble in water.

[0276] The aforementioned cleaning accelerator is a component that improves the cleaning (developing) ability of the developer by being used in combination with the aforementioned surfactant and pH adjuster.

[0277] Examples of the cleaning accelerator include, but are not limited to, amines such as monoethanolamine, diethanolamine, and triethanolamine, ammonium salts such as tetramethylammonium hydroxide, and paraffin-based hydrocarbons.

[0278] One or more selected from the group consisting of nonionic, anionic and other surfactants, pH adjusters and cleaning accelerators can be added to the developer in an amount of preferably 0.1 to 50% by mass, more preferably 1 to 10% by mass.

[0279] During development, ultrasonic waves or the like may be used to provide vibration to the flexographic printing plate, or the surface of the printing plate may be rubbed mechanically using a brush or the like.

[0280] In order to obtain a flexographic printing plate that can print brightly and has excellent ink smearing and ink transfer properties, it is preferred to mix 0.01% by mass to 5% by mass of a siloxane compound in a solvent-based or water-based developer.

[0281] That is, the flexographic printing plate of the present embodiment is preferably a flexographic printing plate obtained by developing the flexographic printing original plate in a developer containing 0.01% by mass to 5% by mass of a siloxane compound when developing the flexographic printing original plate after pattern formation and exposure.

[0282] Examples of the siloxane compound include, but are not limited to, silicone oil containing a siloxane unit (hereinafter simply referred to as silicone oil), a silane coupling agent, a silane compound, silicone rubber, and a silicone resin.

[0283] Among the above-mentioned siloxane compounds, the siloxane compound contained in the developer is preferably a silicone oil modified with an amino group, a polyether group, a carbinol group or the like.

[0284] As the post-exposure treatment, there is a method of irradiating the surface with light having a wavelength of 300 nm or less. If necessary, light having a longer wavelength than 300 nm may be used in combination.

[0285] The photosensitive resin composition layer of the flexographic printing original plate of the present embodiment is useful for both solvent development and thermal development, and can be preferably used for solvent development in particular from the viewpoint of high image reproducibility of the printing plate.

[0286] In addition, the method for manufacturing a flexographic printing plate of the present embodiment can obtain bright printing. From the viewpoint of obtaining a flexographic printing plate with excellent ink paste and ink transfer properties, it is preferred to coat the developed flexographic printing plate with a silicone component and / or a fluorine-based compound before post-processing exposure.

[0287] That is, the flexographic printing plate of the present embodiment is preferably a flexographic printing plate obtained by subjecting a flexographic printing original plate to patterning, exposure, and development, and then coating with a silicone component and / or a fluorine-based compound.

[0288] The siloxane component applied to the plate after development may be a reactive siloxane or a non-reactive siloxane, and a (meth)acrylic acid-modified siloxane may be preferably used.

[0289] In addition, as the fluorine-based compound applied after development, for example, polyfluoroethylene compounds, poly(ethylene-fluoroethylene) compounds, acrylic copolymers having perfluoroalkyl groups in the side chains, urethane polymers having perfluoroalkyl groups, ester polymers having perfluoroalkyl groups, or fluorine-based monomers can be appropriately listed.

[0290] The siloxane component and the fluorine-based compound may be used alone or in combination of two or more.

[0291] The siloxane component and / or the fluorine-based compound may be used by dissolving in a solvent to form a solution.

[0292] As the solvent, a solvent that adheres to the surface of the printing plate and permeates near the surface is suitable. By selecting a solvent that permeates the surface of the printing plate and treating it in the post-exposure process, the siloxane component and / or the fluorine-based compound can be further firmly adhered to the plate surface (nearby).

[0293] The concentration of the siloxane component and / or the fluorine-based compound in the solution containing the siloxane component and / or the fluorine-based compound is preferably 0.05 to 50% by mass.

[0294] The solvent is not limited to the following, and solvents such as hydrocarbons, acetates, alcohols, ketones, and glycol ethers can be used. These can be used alone or in combination of two or more.

[0295] In order to impregnate the surface of the printing plate, water and the above-mentioned solvents such as paraffin or glycol ether may be used in combination, or a nonionic surfactant having a high penetrating power may be added.

[0296] If necessary, additives such as a defoaming agent, an antioxidant or a preservative may be added to the solution containing the silicone component and / or the fluorine-based compound.

[0297] Examples of the coating method for the surface of the developed flexographic printing plate include solution coating by spraying, brushing, dipping, coating with a cloth or sponge, adding a rinse solution after development and dripping onto the surface, etc. Among these, solution coating by spraying is preferred.

[0298] The coating may be performed immediately after development if it is before post-exposure, or may be performed after development and drying.

[0299] Example

[0300] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples at all.

[0301] [Production Example 1]

[0302] (Synthesis of Hydrophilic Copolymer)

[0303] In a pressure-resistant reaction vessel equipped with a stirring device and a temperature regulating jacket, 125 parts by mass of water and 2 parts by mass of (α-sulfo(1-nonylphenoxy)methyl-2-(2-propyleneoxy)ethoxy-poly(oxy-1,2-ethanediyl)ammonium salt "ADEKAREASOAP" (manufactured by Asahi Denka Industries) as a reactive emulsifier were initially charged, the internal temperature was raised to 80°C, and an oily mixed liquid containing a monomer mixture of 10 parts by mass of styrene, 60 parts by mass of butadiene, 23 parts by mass of butyl acrylate, 5 parts by mass of methacrylic acid, and 2 parts by mass of acrylic acid and 2 parts by mass of tert-dodecyl mercaptan and an aqueous solution containing 28 parts by mass of water, 1.2 parts by mass of sodium persulfate, 0.2 parts by mass of sodium hydroxide, and 2 parts by mass of (α-sulfo(1-nonylphenoxy)methyl-2-(2-propyleneoxy)ethoxy-poly(oxy-1,2-ethanediyl)ammonium salt were added at a constant flow rate over 5 hours and 6 hours, respectively.

[0304] The temperature was then maintained at 80°C for 1 hour to complete the polymerization reaction and obtain a copolymer latex, which was then cooled.

[0305] Furthermore, the pH of the generated copolymer latex was adjusted to 7 with sodium hydroxide, unreacted monomers were removed by steam stripping, and the mixture was filtered through a 200-mesh wire mesh to finally adjust the solid content concentration of the filtrate to 40% by mass, thereby obtaining an aqueous dispersion of a hydrophilic copolymer.

[0306] The obtained aqueous dispersion of the hydrophilic copolymer was dried thoroughly in a vacuum dryer at 50° C. to remove water, thereby obtaining a hydrophilic copolymer.

[0307] [Production Example 2]

[0308] (Production of base film (support))

[0309] As a solution for an adhesive layer to be applied to a support (base film), 55 parts by mass of Tufprene 912 (trade name, manufactured by Asahi Kasei Corporation) which is a block copolymer of styrene and 1,3-butadiene, 38 parts by mass of paraffin oil (average carbon number 33, average molecular weight 470, density at 15° C. 0.868), 2.5 parts by mass of 1,9-nonanediol diacrylate, 1.5 parts by mass of 2,2-dimethoxy-phenylacetophenone, 3 parts by mass of EPOXY ESTER 3000M (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), and 1.5 parts by mass of Balifast YELLOW 3150 (trade name, manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) were dissolved in toluene to obtain a solution having a solid content of 25%.

[0310] Then, the mixture was applied on one side of a 100 μm thick polyester film using a knife coater so that the ultraviolet transmittance was 10%, and dried at 80° C. for 1 minute to obtain a support (base film) having an adhesive layer.

[0311] The UV transmittance of the support was calculated by measuring the transmission intensity using an ultraviolet exposure machine AFP-1500 (trade name, manufactured by Asahi Kasei Corporation) with a UV illuminometer MO-2 (trade name, UV-35 Filter, manufactured by ORC MANUFACTURING CO., LTD.).

[0312] [Production Example 3]

[0313] (Fabrication of a thin film with an infrared ablation layer)

[0314] 65 mass % of Asaflex 810 (trade name, manufactured by Asahi Kasei Corporation) which is a block copolymer of styrene and 1,3-butadiene and 35 mass % of carbon black which is an infrared sensitive material were kneaded by a kneader and cut into pellets. Then, 90 mass parts of the pellets and 10 mass parts of 1,6-hexanediol adipate were dissolved by ultrasonic wave in a mixed solvent prepared in a mass ratio of ethyl acetate / butyl acetate / propylene glycol monomethyl ether acetate = 50 / 30 / 20 to prepare a uniform solution having a solid content of 12 mass %.

[0315] Then, the solution is applied in a dry coating amount of 4 to 5 g / m 2 The film was coated on a polyester film having a thickness of 100 μm, which served as a cover sheet, using a knife coater and dried at 80° C. for 1 minute to obtain a film having an ultraviolet shielding layer (infrared ablation layer) that could be cut by infrared rays.

[0316] The optical density of the thin film having an infrared ablation layer was measured by DM-500 (trade name, manufactured by Dainippon Screen Mfg. Co., Ltd.) and was 3 to 4.

[0317] [Production Example 4]

[0318] (Production of Cover Film (Film Having Intermediate Layer and Infrared Ablation Layer))

[0319] 75% by mass of water-soluble polyamide (PA, AQ Nylon T-70 manufactured by Toray Industries, Inc.), 5% by mass of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation), 10% by mass of water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation), and 10% by mass of modified silicone oil (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.) were added to a solution prepared in a mass ratio of ethanol / distilled water = 10 / 90, and the mixture was stirred to prepare an intermediate layer coating liquid.

[0320] Next, the intermediate layer coating liquid was applied to the infrared ablation layer-forming surface of the infrared ablation layer-having film produced in [Production Example 3] using a bar coater so that the film thickness after drying would be 3 μm.

[0321] Then, the film was dried at 100° C. for 4 minutes to obtain a cover film having an intermediate layer and an infrared ablation layer.

[0322] [Example 1]

[0323] (Production of flexographic printing plates)

[0324] 32 parts by mass of the hydrophilic copolymer obtained in the above [Production Example 1] and 28 parts by mass of a styrene-butadiene-styrene copolymer [D-KX405: manufactured by Kraton Corporation] were mixed at 140° C. using a pressure kneader, and then a liquid mixture of 32 parts by mass of liquid polybutadiene [LBR-352: manufactured by KURARAY CO., LTD.], 8 parts by mass of 1,9-nonanediol diacrylate, 5 parts by mass of 1,6-hexanediol dimethacrylate, 2 parts by mass of 2,2-dimethoxyphenylacetophenone, 1 part by mass of 2,6-di-tert-butyl-p-cresol, and 1 part by mass of carbinol-modified silicone oil [KF-6000: manufactured by Shin-Etsu Chemical] was added little by little over 15 minutes. After the addition was completed, the mixture was further kneaded for 20 minutes to obtain a photosensitive resin composition.

[0325] The film was then placed in an extruder, and the base film (support) obtained in [Manufacturing Example 2] was bonded to one side of the photosensitive resin composition layer extruded and molded by the T-die. A release film (DIAFOIL MRV100 manufactured by Mitsubishi Chemical Corporation) was further bonded to the side of the photosensitive resin composition layer opposite to the support laminated side, thereby obtaining a laminate of the support and the photosensitive resin composition layer.

[0326] Next, the release film was peeled off, and the cover film having the intermediate layer and the infrared ablative layer obtained in [Production Example 4] was laminated so that the intermediate layer was in contact with the photosensitive resin composition layer to obtain a flexographic printing plate.

[0327] (Manufacture of flexographic printing plates)

[0328] The flexographic printing plate was exposed from the support (PET coated with an adhesive) side using an ultraviolet exposure device (JE-A2-SS manufactured by JEOL Precision Machinery) so that the pattern height (RD) after curing was about 0.6 mm.

[0329] Next, the cover sheet of the infrared ablation layer was peeled off, and a dot image (AM150 line, data 1% dot) was drawn on the infrared ablation layer using an ESKO laser drawing machine (CDI), and then the infrared ablation layer side was exposed to 8000mJ in an atmospheric atmosphere using the aforementioned exposure machine.

[0330] After exposure, an aqueous solution (aqueous developer) of 1% polyoxyalkylene alkyl ether (Newcol 2308: manufactured by Nippon Emulsifier) ​​and 1% potassium carbonate was prepared and washed (developed) at 40°C using a Nippon Denshi Seiki washing machine (JOW-A3-P) to remove unexposed areas.

[0331] After drying at 50° C. for 10 minutes, post-exposure was performed using an ultraviolet sterilization lamp and an ultraviolet chemical lamp to remove surface stickiness, thereby obtaining a flexographic printing plate.

[0332] [Example 2]

[0333] In the manufacture of the flexographic printing plate, when the intermediate layer coating liquid described in the above [Manufacturing Example 4] was manufactured, sodium carboxymethylcellulose (CMC, manufactured by Wako Pure Chemical Industries, Ltd.) was used instead of water-soluble polyamide (PA). Other conditions were the same as [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0334] [Example 3]

[0335] In the production of the flexographic printing plate, polyvinyl alcohol (PVA KURARAY CO., LTD., Poval PVA-205) was used instead of water-soluble polyamide (PA) when producing the intermediate layer coating liquid described in [Production Example 4]. Other conditions were the same as [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0336] [Example 4]

[0337] In the production of the flexographic printing plate, in the production of the intermediate layer coating solution described in [Production Example 4], water-soluble polyurethane (HYDRAN WLS-202 manufactured by PU DIC) was used instead of water-soluble polyamide (PA). Other conditions were the same as [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0338] [Example 5]

[0339] In the manufacture of the flexographic printing plate, when the intermediate layer coating liquid described in the above [Manufacturing Example 4] was manufactured, 55% by mass of water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 10% by mass of water-swellable synthetic mica (manufactured by Katakura & Co-op Agri Corporation, Somasif MEB-3 aqueous solution), 10% by mass of water-dispersible latex (manufactured by Asahi Kasei Corporation, L7430), and 10% by mass of modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., KF-351A) were used. Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0340] [Example 6]

[0341] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the above [Preparation Example 4], 70% by mass of water-soluble polyamide (PA, AQ Nylon T-70 manufactured by Toray Industries, Inc.) and 10% by mass of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation) were used. Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0342] [Example 7]

[0343] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the above [Preparation Example 4], 79% by mass of water-soluble polyamide (PA, AQ Nylon T-70 manufactured by Toray Industries, Inc.) and 1% by mass of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation) were used. Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0344] [Example 8]

[0345] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the aforementioned [Preparation Example 4], water-swellable synthetic mica (Somasif ME-100 aqueous solution manufactured by Katakura & Co-op Agri Corporation) was used instead of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation). Other conditions were the same as those in the aforementioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0346] [Example 9]

[0347] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the aforementioned [Preparation Example 4], montmorillonite (KUNIMINE INDUSTRIES CO., LTD., Kunipia) was used instead of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation). Other conditions were the same as those in the aforementioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0348] [Example 10]

[0349] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the above [Preparation Example 4], montmorillonite (KUNIMINE INDUSTRIES CO., LTD., Sumecton) was used instead of water-swellable synthetic mica (Somasif MEB-3 aqueous solution, manufactured by Katakura & Co-op Agri Corporation). Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0350] [Example 11]

[0351] In the preparation of the flexographic printing plate, the intermediate layer coating solution described in the above [Preparation Example 4] was prepared and applied so that the film thickness of the intermediate layer was 2.0 μm. Other conditions were the same as in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0352] [Example 12]

[0353] In the preparation of the flexographic printing plate, the intermediate layer coating solution described in the above [Preparation Example 4] was prepared and applied so that the film thickness of the intermediate layer was 10 μm. Other conditions were the same as in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0354] [Example 13]

[0355] In the preparation of the flexographic printing plate, the intermediate layer coating solution described in the above [Preparation Example 4] was prepared and applied so that the film thickness of the intermediate layer was 30 μm. Other conditions were the same as in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0356] [Example 14]

[0357] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the aforementioned [Manufacturing Example 4], 60% by mass of water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70) and 25% by mass of water-dispersible latex (manufactured by Asahi Kasei Corporation, L7430) were used. Other conditions were the same as those in the aforementioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0358] [Example 15]

[0359] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the above [Manufacturing Example 4], 80% by mass of water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70) and 5% by mass of water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation) were used. Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0360] [Example 16]

[0361] In the preparation of the flexographic printing plate, when preparing the intermediate layer coating solution described in the above [Manufacturing Example 4], 75% by mass of water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70) and 10% by mass of water-dispersible latex (manufactured by Asahi Kasei Corporation, XL-006) were used. Other conditions were the same as those in the above [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0362] [Example 17]

[0363] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 85% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 5% by mass of a water-swellable synthetic mica (manufactured by Katakura & Co-op Agri Corporation, Somasif MEB-3 aqueous solution), and 10% by mass of a modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., KF-351A) were used.

[0364] In addition, water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation) was not used.

[0365] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0366] [Example 18]

[0367] In the production of a flexographic printing plate, when producing the intermediate layer coating solution described in the aforementioned [Production Example 4], 75% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 5% by mass of a water-swellable synthetic mica (manufactured by Katakura & Co-op Agri Corporation, Somasif MEB-3 aqueous solution), 8% by mass of a water-dispersible latex (manufactured by Zeon Corporation, Nipol SX1503A), and 10% by mass of a modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., KF-351A) were used.

[0368] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0369] [Example 19]

[0370] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 75% by mass of a water-soluble polyamide (PA, AQ Nylon T-70 manufactured by Toray Industries, Inc.), 5% by mass of boehmite (alumina sol F-3000 manufactured by Kawaken Fine Chemicals Co., Ltd.), 10% by mass of a water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.) are used.

[0371] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0372] [Example 20]

[0373] In the production of a flexographic printing plate, when producing the intermediate layer coating solution described in the aforementioned [Production Example 4], 75% by mass of polyvinyl pyrrolidone (PVP, K60, manufactured by Sigma-Aldrich Co., LLC), 5% by mass of water-swellable synthetic mica (Somasif MEB-3 aqueous solution, manufactured by Katakura & Co-op Agri Corporation), 10% by mass of a water-dispersible latex (L7430, manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A, manufactured by Shin-Etsu Chemical Co., Ltd.) were used.

[0374] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0375] [Example 21]

[0376] In the production of a flexographic printing plate, when producing the intermediate layer coating solution described in the aforementioned [Production Example 4], 75% by mass of poly 2-ethyloxazoline (POx manufactured by Sigma-Aldrich Co. LLC, Mw 50,000 or less), 5% by mass of water-swellable synthetic mica (Somasif MEB-3 aqueous solution manufactured by Katakura & Co-op Agri Corporation), 10% by mass of a water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.) were used.

[0377] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0378] [Example 22]

[0379] In the production of a flexographic printing plate, when producing the intermediate layer coating solution described in the aforementioned [Production Example 4], 75% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 5% by mass of aluminum hydroxide particles (Serath 05070 manufactured by Kinsei Matec Co., Ltd.), 10% by mass of a water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.) were used.

[0380] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0381] [Example 23]

[0382] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 75% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 5% by mass of barium titanate particles (Tismo N, manufactured by Otsuka Chemical Co., Ltd.), 10% by mass of a water-dispersible latex (L7430, manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A, manufactured by Shin-Etsu Chemical Co., Ltd.) were used.

[0383] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0384] [Example 24]

[0385] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 75% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 5% by mass of boehmite (manufactured by Kawaken Fine Chemicals Co., Ltd., alumina sol 5N), 10% by mass of a water-dispersible latex (manufactured by Asahi Kasei Corporation, L7430), and 10% by mass of a modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., KF-351A) are used.

[0386] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0387] [Comparative Example 1]

[0388] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 80% by mass of a water-soluble polyamide (PA, manufactured by Toray Industries, Inc., AQ Nylon T-70), 10% by mass of a water-dispersible latex (L7430 manufactured by Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A manufactured by Shin-Etsu Chemical Co., Ltd.) were used.

[0389] It should be noted that no inorganic layered compound was used.

[0390] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0391] [Comparative Example 2]

[0392] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the above [Production Example 4], silica particles (Snowtex ST-30L aqueous dispersion produced by Nissan Chemical Co., Ltd.) were used instead of water-swellable synthetic mica (Somasif MEB-3 aqueous solution produced by Katakura & Co-op Agri Corporation).

[0393] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0394] [Comparative Example 3]

[0395] In the production of the flexographic printing plate, when the intermediate layer coating liquid described in the above-mentioned [Production Example 4] was produced, the film thickness of the intermediate layer was adjusted to be 1.5 μm and applied.

[0396] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0397] [Comparative Example 4]

[0398] In the production of the flexographic printing plate, when the intermediate layer coating liquid described in the above-mentioned [Production Example 4] was produced, the intermediate layer was coated while being adjusted so that the film thickness was 40 μm.

[0399] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0400] [Comparative Example 5]

[0401] In the production of a flexographic printing plate, when producing the intermediate layer coating liquid described in the aforementioned [Production Example 4], 80% by mass of polyvinyl alcohol (PVA KURARAY CO., LTD., Poval PVA-205), 10% by mass of a water-dispersible latex (L7430, Asahi Kasei Corporation), and 10% by mass of a modified silicone oil (KF-351A, Shin-Etsu Chemical Co., Ltd.) are used.

[0402] It should be noted that no inorganic layered compound was used.

[0403] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0404] [Comparative Example 6]

[0405] In the production of the flexographic printing plate, the film having an infrared ablative layer described in the above [Production Example 3] was used instead of the cover film described in the above [Production Example 4].

[0406] The other conditions were the same as those in the above-mentioned [Example 1] to obtain a flexographic printing original plate and a flexographic printing plate.

[0407] In the above, an example of performing development treatment using an aqueous developer to remove unexposed portions is shown, but the method for producing a flexographic printing plate of the present embodiment is not limited to this example, and development treatment may be performed using a solvent-based developer.

[0408] [Characteristics evaluation]

[0409] (Evaluation of Flexographic Printing Plate)

[0410] <Pinhole Evaluation>

[0411] Five pieces of the flexographic printing plates obtained in Examples and Comparative Examples were cut into a size of 10 cm×10 cm to prepare samples.

[0412] In these samples, the cover sheet of the infrared ablation layer was removed and the samples were placed on a photometer stage for microscopic examination.

[0413] In the infrared ablation layer, the number of pinholes with a major diameter of 20 μm or more was counted, and the average value was obtained to calculate (number / m 2 ) is evaluated by the following 1 to 5. In the following evaluation, if it is 3 or more, it can be used practically without any problem.

[0414] 5: The number of pinholes is less than the average of 2 ( / m 2 ).

[0415] 4: The number of pinholes is an average of 2 ( / m 2 ) and less than 5 (pieces / m 2).

[0416] 3: The number of pinholes is an average of 5 ( / m 2 ) and less than 10 (pieces / m 2 ).

[0417] 2: The number of pinholes is an average of 10 (pieces / m 2 ) and less than 20 (pieces / m 2 ).

[0418] 1: The number of pinholes is an average of 20 (pieces / m 2 )above.

[0419] <Pinhole evaluation during high humidity storage>

[0420] The cover film having the intermediate layer and the infrared ablative layer obtained in the above-mentioned [Production Example 4] was stored in an environment of 40° C. and a relative humidity of 10% for one week.

[0421] Then, the flexographic printing plate prepared in the same manner as in [Example 1] was cut into five pieces having a size of 10 cm×10 cm to prepare samples.

[0422] In these samples, the cover sheet of the infrared ablation layer was removed and the samples were placed on a photometer stage for microscopic examination.

[0423] In the infrared ablation layer, the number of pinholes with a major diameter of 20 μm or more was counted, and the average value was obtained to calculate (number / m 2 ) is evaluated by the following 1 to 5. In the following evaluation, if it is 3 or more, it can be used practically without any problem.

[0424] 5: The number of pinholes is less than the average of 2 ( / m 2 ).

[0425] 4: The number of pinholes is an average of 2 ( / m 2 ) and less than 5 (pieces / m 2 ).

[0426] 3: The number of pinholes is an average of 5 ( / m 2 ) and less than 10 (pieces / m 2 ).

[0427] 2: The number of pinholes is an average of 10 (pieces / m 2 ) and less than 20 (pieces / m 2 ).

[0428] 1: The number of pinholes is an average of 20 (pieces / m 2 )above.

[0429] <Evaluation of cleaning performance>

[0430] The flexographic printing original plate was exposed from the support side for 60 seconds using an ultraviolet exposure machine "JE-A2-SS" (trade name, manufactured by Nippon Denshi Seiki Co., Ltd.).

[0431] Then, the cover sheet as the upper layer of the infrared ablation layer was peeled off, and the support body side was placed in contact with the drum of CDI Spark4260 (manufactured by ESKO GRAPHIC Co., Ltd., trade name), and 1% dots (AM150 lines / inch) (resolution 2540 dpi) were drawn on the infrared ablation layer using a fiber laser (wavelength 1070 nm) at an output power of 18.2 W and a rotation speed of 200 rpm. Then, exposure was performed for 12 minutes using the aforementioned exposure machine (illuminance 10 mW).

[0432] Next, a water-based developer containing 5 parts by mass of "LEOCOL SC-80" (Lion Corporation, trade name, HLB 12.7), which is a 5-mol adduct of ethylene oxide of a secondary alcohol having 12 to 14 carbon atoms, as a surfactant, 1 part by mass of dibutyl diglycol as an impregnating agent, and 0.4 parts by mass of sodium carbonate was used, and washing was performed at 40°C using a flat-type washing machine (manufactured by RoboElectronis). After 1 minute, 2 minutes, and 3 minutes of washing, the removal of the infrared ablation layer in the non-image area was confirmed. Then, washing was further performed for 17 minutes, for a total of 20 minutes.

[0433] The film was then dried at 60°C for 15 minutes and post-exposure treated using a chemical lamp and a germicidal lamp.

[0434] The observation results of the removal status of the infrared ablation layer were evaluated according to the following criteria.

[0435] In the following evaluation criteria, if it is 3 or more, it can be used practically without any problem.

[0436] 5. When the washing time is 1 minute, the infrared ablation layer can be removed evenly.

[0437] 4. When the washing time is 1 minute, the infrared ablation layer cannot be removed uniformly, but it can be removed uniformly when the washing time is 2 minutes.

[0438] 3. When the washing time is 2 minutes, the infrared ablation layer cannot be removed uniformly, but it can be removed uniformly when the washing time is 3 minutes.

[0439] 2. The infrared ablation layer can be removed within the normal washing time (20 minutes).

[0440] 1. Residual spots, the infrared ablation layer cannot be removed evenly.

[0441] (Evaluation of Flexographic Printing Plates)

[0442] Using the flexographic printing plates obtained in Examples and Comparative Examples, actual printing evaluation was performed.

[0443] An AI-3 flexographic printing machine (manufactured by Iyo Machinery) was used, Process X cyan (manufactured by TOYO INK CO., LTD., trade name) was used as the solvent ink, and an OPP film was used as the printed object.

[0444] In addition, the anilox roller uses 800lpi (box volume 3.8cm 3 / m 2 ), the buffer belt used was 3M1020 (manufactured by Sumitomo 3M Limited., trade name), the printing speed was 100 m / min, and the printing length was 3000 m.

[0445] <Reproducibility of small prints>

[0446] Print reproducibility refers to a property of evaluating whether the shape and size of the tops of dots formed on a flexographic printing plate are the same as the shape and size of dots on a printed matter.

[0447] In this evaluation, small dots (AM150 lines, 1% dot portion) of the halftone dot image portion on the flexographic printing plate were observed using FLEX 3PRO (manufactured by Avid Flex CO., LTD.), and halftone dots on the printed matter were observed using a 150x microscope (manufactured by KEYENCE CORPORATION, VHX-1000).

[0448] The evaluation criteria of the observation results are as follows.

[0449] In the following evaluation criteria, if it is 3 or more, it can be used practically without any problem.

[0450] 4: The tops of the dots on the flexographic printing plate and the dots on the printed matter are all circular, and the reproducibility of shape and size is high.

[0451] 3: The tops of the dots on the flexographic printing plate and the dots on the printed matter are both circular, but the reproducibility of the dot size is low.

[0452] 2: The tops of the dots on the flexographic printing plate were circular, but the dots on the printed matter were elliptical and connected lines were observed, indicating low reproducibility.

[0453] 1: The dots on the flexographic printing plate have rounded tops and are poorly formed. There are no dots on the printed material.

[0454] <Ink paste version>

[0455] The flexographic printing plate obtained after the above printing for 3000 m was observed with a magnifying glass at the 3% halftone dots and 30% halftone dots and between the dots (concave portions) in the halftone dot portion of the flexographic printing plate.

[0456] The evaluation criteria of the observation results are as follows.

[0457] In the following evaluation criteria, if it is 2 or more, it can be used practically without any problem.

[0458] 3: Ink is applied only to the upper layer of the shoulder of the dot.

[0459] 2: The ink flows to the middle of the dot.

[0460] 1: The ink flows to the bottom between the dots.

[0461] (Thickness of the middle layer)

[0462] The flexographic printing plate was exposed from the support side for 600 seconds using an ultraviolet exposure machine. After the plate was photocured, the sample was processed using a FIB (Focused Ion Beam) device, and the exposed cross section was observed using a SEM (scanning electron microscope) to evaluate the film thickness of the intermediate layer.

[0463] (Gel fraction of middle layer)

[0464] The intermediate layer coating liquid obtained in the above-mentioned "Manufacturing Example 4" was dried to obtain a solid. The mass of the obtained solid was measured. The mass of the intermediate layer was then measured after being immersed in pure water at room temperature for 72 hours and then dried at 50°C for 3 hours, and the value calculated by the following formula was taken as the gel fraction.

[0465] Gel fraction (%) = (mass of the intermediate layer after being immersed in pure water at room temperature for 72 hours and then dried at 50°C for 3 hours / mass of the intermediate layer before being immersed in pure water) × 100

[0466] The composition of the intermediate layer used in the flexographic printing original plates and flexographic printing plates of Examples 1 to 24 and Comparative Examples 1 to 6, the film thickness of the intermediate layer, the gel fraction, and the above-mentioned evaluation results are shown in Tables 1 and 2 below.

[0467] [Table 1]

[0468]

[0469] [Table 2]

[0470]

[0471] This application is based on Japanese Patent Application (Japanese Patent Application No. 2018-230516) filed with the Japan Patent Office on December 10, 2018, the contents of which are incorporated herein by reference.

[0472] Industrial Applicability

[0473] The flexographic printing original plate and the flexographic printing plate of the present invention have industrial applicability in the field of printing requiring prevention of plate surface contamination and brightness.

Claims

1. A flexographic printing plate, which is a flexographic printing plate in which at least a support, a photosensitive resin composition layer, an intermediate layer and an infrared ablation layer are sequentially stacked, The intermediate layer contains a hydrophilic resin (A) and an inorganic stratiform compound (B), wherein the intermediate layer contains 0.1 to 20 parts by mass of the inorganic stratiform compound (B) based on 100 parts by mass of the hydrophilic resin (A). The hydrophilic resin (A) contains functional groups capable of covalently bonding and / or ionically bonding with clay minerals. The inorganic layered compound (B) is a clay mineral that is swellable in water. The intermediate layer further contains a water-dispersible latex (C), wherein the intermediate layer contains 5 to 45 parts by weight of the water-dispersible latex (C) based on 100 parts by weight of the hydrophilic resin (A). The intermediate layer has a thickness of 2 μm or more and 30 μm or less.

2. A flexographic printing plate, which is a flexographic printing plate in which at least a support, a photosensitive resin composition layer, an intermediate layer and an infrared ablation layer are laminated in this order, The intermediate layer contains a hydrophilic resin (A) and an inorganic stratiform compound (B), wherein the intermediate layer contains 0.1 to 20 parts by mass of the inorganic stratiform compound (B) based on 100 parts by mass of the hydrophilic resin (A). The hydrophilic resin (A) contains functional groups capable of covalently bonding and / or ionically bonding with clay minerals. The inorganic layered compound (B) is a crystalline inorganic fine particle dispersed in water. The intermediate layer further contains a water-dispersible latex (C), wherein the intermediate layer contains 5 to 45 parts by weight of the water-dispersible latex (C) based on 100 parts by weight of the hydrophilic resin (A). The intermediate layer has a thickness of 2 μm or more and 30 μm or less.

3. The flexographic printing original plate according to claim 1 or 2, wherein: The intermediate layer is water-soluble or alkali-soluble.

4. The flexographic printing original plate according to claim 1, wherein The clay mineral is selected from kaolinite, dickite, halloysite, talc, pyrophyllite, saponite, lithium magnesium silicate, montmorillonite, beidellite, vermiculite or mica.

5. The flexographic printing original plate according to claim 1, wherein The inorganic layered compound (B) is water-swellable synthetic mica.

6. The flexographic printing original plate according to claim 1 or 2, wherein: The average particle size of the inorganic layered compound (B) is 1 μm or more and 10 μm or less.

7. The flexographic printing original plate according to claim 1 or 2, wherein: The thickness of the inorganic layered compound (B) is 10 nm or more and 500 nm or less.

8. The flexographic printing original plate according to claim 1 or 2, wherein: The content of the water-dispersible latex (C) is 10% by mass or more and 80% by mass or less based on the total amount of the intermediate layer.

9. The flexographic printing original plate according to claim 1 or 2, wherein: The gel fraction of the intermediate layer calculated by the following formula is 10% to 90%, Gel fraction (%)=(mass of the intermediate layer after being immersed in pure water at room temperature for 72 hours and then dried at 50° C. for 3 hours / mass of the intermediate layer before being immersed in pure water)×100.

10. The flexographic printing original plate according to claim 1 or 2, wherein: The material of the photosensitive resin composition layer is a photosensitive resin composition containing (a) a thermoplastic elastomer, (b) a hydrophilic copolymer, (c) a photopolymerizable monomer, and (d) a photopolymerization initiator.

11. A method for manufacturing a flexible printing plate, comprising the following steps: A step of laser ablating the infrared ablation layer of the flexographic printing plate according to any one of claims 1 to 10 to produce a negative pattern; A step of selectively exposing the photosensitive resin composition layer through the negative pattern; and A step of removing the unexposed portion of the photosensitive resin composition layer.

12. The manufacturing method according to claim 11, further comprising the following steps: Before the infrared ablation layer is laser ablated, ultraviolet light exposure, namely, back exposure, is performed on the entire surface through the support of the flexographic printing original plate to cure the photosensitive resin composition layer to form a thin uniform cured layer. 13 . The manufacturing method according to claim 11 , further comprising the step of: after the step of removing the unexposed portion, performing post-processing exposure to obtain the flexographic printing plate.